Method for sintering YAG layer

Through the combination of yttrium oxide and alumina powder with specific particle size distribution and pressure-assisted sintering technology, a high-purity and high-density polycrystalline yttrium aluminum garnet (YAG) sintered ceramic body is produced, and the large-sized sintered body in the prior art is solved. Corrosion and erosion problems under plasma conditions have achieved efficient etching and erosion resistance.

CN119451925APending Publication Date: 2025-02-14HERAEUS CONAMIC NORTH AMERICA LLC
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
CN202380049755.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-07-21
Filing Date
2023-07-14
Publication Date
2025-02-14

AI Technical Summary

Technical Problem

It is difficult to manufacture high-purity and high-density large-size yttrium aluminum oxide sintered bodies in the prior art. Especially under plasma etching and deposition conditions, the materials are prone to corrosion and erosion, resulting in loss of yield of semiconductor devices.

Method used

By combining yttrium oxide powder and alumina powder at a specific particle size distribution, pressure assisted sintering technology is used to heat and apply pressure under vacuum conditions and form a sintering containing 90% to 99.8% by volume of polycrystalline yttrium aluminum garnet (YAG) Ceramic body.

Benefits of technology

The sintered ceramic body with high purity, high density and low porosity is achieved, and corrosion resistance and corrosion resistance are enhanced under plasma etching and deposition conditions, and is suitable for the components required for the manufacturing of large-sized semiconductor devices.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119451925A_ABST
    Figure CN119451925A_ABST
Patent Text Reader

Abstract

Disclosed herein is a method for preparing a sintered ceramic body comprising at least one layer of 99 vol% or more polycrystalline yttrium aluminum garnet (YAG) substantially free of unreacted yttrium oxide and yttrium-rich phase by sintering and in situ reaction of yttrium oxide with alumina comprising fine and coarse particle sizes.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure relates to corrosion resistant sintered ceramic bodies and parts formed therefrom, methods of producing the sintered ceramic bodies, and use in semiconductor plasma processing chambers. The sintered ceramic bodies are substantially free of defects, making them particularly resistant to etching and erosion from plasma conditions. Background Art

[0002] Semiconductor processing requires the use of halogen-based gases and a combination of oxygen and other gases with high electric and magnetic fields to form a plasma etching environment. The plasma etching environment is generated in a vacuum chamber for etching materials on a semiconductor substrate. Harsh plasma etching environments require the use of highly corrosion-resistant materials for chamber components. These chambers include components such as disks or windows, pads, gas injectors, rings, and cylinders, which confine plasma to the wafer being processed. These components have been formed by materials that provide corrosion and erosion tolerance in a plasma environment, and have been described, for example, in US 5,798,016, US 5,911,852, US 6,123,791, and US 6,352,611. However, these parts used in plasma processing chambers are continuously subject to plasma erosion, and therefore corrode, erode, and roughen on the surface of chamber components exposed to plasma. This corrosion and erosion contribute to wafer-level contamination by releasing particles from the surface of the components into the chamber, thereby causing a yield loss of semiconductor devices.

[0003] Rare earth oxides are known, and among them yttrium aluminum garnet (YAG) (Y3Al5O 12 , cubic phase) and the related yttrium aluminum oxide family such as YAP (AlYO3) and YAM (Y4Al2O9) have a wide range of technical and industrial applications. YAG with a cubic crystalline phase has received a lot of attention due to applications such as host materials for solid-state lasers, transparent armor, ballistic infrared window materials, and their combination of mechanical, thermal and optical characteristics. Especially for laser applications, single crystal YAG is an ideal substrate due to its ability to accommodate rare earth dopants, so a lot of effort has been made to produce single crystal YAG. In addition to optical applications, YAG is also known to be very chemically inert and exhibits high halogen-based plasma corrosion resistance and erosion resistance.

[0004] Sintering YAG-based ceramics to high densities required for advanced applications that require minimal residual porosity in the final component is challenging. For semiconductor applications involving plasma corrosion, porosity accelerates chemical attack on the surface of chamber components and produces particles when the surface degrades with long-term use. As is familiar to those skilled in the art, in addition to reduced chemical resistance, excessive porosity can be detrimental to the mechanical and thermal properties of the ceramic. Densification of YAG ceramics typically requires vacuum sintering at high temperatures of about 1600°C and higher for an extended period of time, such as 8 hours or more, to achieve a theoretical density of >98%. In order to achieve a higher density close to the theoretical value, pressure-assisted densification techniques, such as hot isostatic pressing (HIP), are used after first vacuum sintering to about 98% density or directly from powder uniaxial hot pressing (HP). Typically, high temperatures and longer sintering durations can lead to excessive grain growth, which adversely affects the mechanical strength of the solid yttrium aluminum oxide body. In order to promote the densification of YAG ceramics, sintering aids, such as silicon dioxide (SiO2), are typically used. However, the addition of sintering aids effectively reduces the corrosion and erosion resistance of the yttrium aluminum oxide material and increases the possibility of impurity contamination at the semiconductor device level during use in the chamber. Therefore, high purity, high density yttrium aluminum oxide body, and especially having a cubic crystalline phase (YAG, Y3Al5O 12 )’s subject is ideal.

[0005] It is known to deposit films or coatings of yttrium aluminum oxide atop a base or substrate formed of a different material that is more readily available and has better mechanical and thermal properties. Such yttrium aluminum oxide films have been produced by several methods. However, these methods are limited in the film thickness that can be produced, manifested by poor adhesion between the film and the substrate, and high levels of volume porosity, resulting in particle shedding into the processing chamber.

[0006] For dense parts made of the YAG phase of yttrium aluminum oxide, a uniform microstructure is preferred to achieve uniform corrosion characteristics over a large area. Therefore, it is desirable to obtain a high phase purity, wherein the majority of the body (>90 volume %) is composed of YAG and a minimum amount of residual phases of aluminum oxide, yttrium oxide, YAP or YAM. However, the manufacture of 100% polycrystalline YAG yttrium aluminum oxide ceramic bodies is very challenging, and therefore trace amounts (<1 volume %) of secondary oxide phases may exist. According to the established yttrium oxide / aluminum oxide phase diagram, YAG exists only as a linear compound according to a stoichiometric composition, and therefore YAG is formed in a phase-pure sintered body only within a very narrow composition range. For this reason, the resulting composition is usually intentionally made to fall on one side or the other of the line. Depending on the intended application, the starting composition is enriched in yttrium oxide or alumina to fall on the selected side of the line.

[0007] Manufacturing ceramic bodies made of YAG for large-scale corrosion-resistant parts is challenging. Solid, phase-pure and high chemical purity parts with a diameter of about 100 mm and larger can be processed and used as a part of a chamber without breaking or cracking, but are difficult to produce beyond laboratory scale. The challenges as mentioned above are mainly attributed to the difficulty of sintering and the physical properties of YAG (including high thermal expansion and low thermal conductivity). There is currently no economically feasible method to manufacture high-purity, crystal-phase pure YAG sintered bodies or parts with a diameter of about 100 mm to about 625 mm and larger for semiconductor etching and deposition applications. High-purity, crystal-phase pure YAG sintered bodies or parts greater than 100 mm are particularly difficult to manufacture.

[0008] One of the difficulties is that YAG is sintered from a mixture of yttria and alumina. In larger sized sintered bodies and parts, there are often regions where the yttria and alumina have not reacted completely. Even if the starting stoichiometry is intentionally made yttria-rich or alumina-rich, the resulting YAG still includes regions of both unreacted yttria and alumina, resulting in a YAG that is not optimal for its intended application.

[0009] Therefore, there is a need for a sintered ceramic body comprising YAG having uniform and high density, low porosity and high purity, providing enhanced plasma corrosion resistance and erosion resistance under plasma etching and deposition conditions, particularly suitable for commercially suitable production methods for manufacturing large-scale components, and which does not contain areas of both unreacted yttrium oxide and aluminum oxide. Summary of the invention

[0010] To meet these and other needs, and in view of its purposes, the present disclosure provides embodiments of multilayer sintered ceramic bodies and methods for making large multilayer sintered ceramic bodies having improved mechanical, electrical, and thermal properties and capable of being processed.

[0011] Embodiment 1. A method for preparing a sintered ceramic body, the method comprising the steps of: a) combining yttrium oxide powder and aluminum oxide powder to prepare a mixture, wherein i) the yttrium oxide powder is characterized by a particle size distribution in which at least 50% by volume of the particles have a size less than 15 microns and the remaining particles have a particle size between 1 micron and 23 microns, and ii) the aluminum oxide powder is characterized by a multimodal particle size distribution including a first maximum and a second maximum of particle sizes on the particle size distribution as a percentage of the particle size, wherein one of the first maximum and the second maximum is between 0.75 microns and 1.35 microns. The invention relates to a method of manufacturing a sintered ceramic body comprising: a) forming a first maximum value and a second maximum value within a particle size range of 100 to 200 μm, wherein the first maximum value and the second maximum value have a particle size greater than the particle size of the other maximum values; b) disposing the mixture in a volume defined by a tool set of a sintering device to form at least one layer of the mixture and to produce a vacuum condition in the volume; c) applying pressure to the at least one layer of the mixture while heating to a sintering temperature and sintering to form a sintered ceramic body, the sintered ceramic body comprising at least one layer containing 90 volume % to 99.8 volume % of polycrystalline yttrium aluminum garnet (YAG); and d) reducing the temperature of the sintered ceramic body.

[0012] Embodiment 2. A method according to Embodiment 1, wherein 15% of the particles of the aluminum oxide powder have a size less than 0.5 microns, 50% of the particles of the aluminum oxide powder have a size less than 2 microns, and 100% of the particles of the aluminum oxide powder have a size less than 15 microns.

[0013] Embodiment 3. A method according to embodiment 2, wherein the first maximum value and the second maximum value are expressed as percentages of the amount of particles, wherein the ratio of the first maximum value to the second maximum value is greater than three.

[0014] Embodiment 4. The method of embodiment 2, wherein the first maximum is a particle size between 3 microns and 5.5 microns.

[0015] Embodiment 5. The method according to embodiment 2, wherein the second maximum is a particle size less than 0.0004 microns.

[0016] Embodiment 6. A method according to Embodiment 2, wherein the multimodal particle size distribution includes a third maximum.

[0017] Embodiment 7. The method according to embodiment 1, wherein the ratio of the first maximum value to the third maximum value is between 2:3 and 9:1.

[0018] Embodiment 8. A method for producing a YAG layer less than 1% alumina-rich in a sintered ceramic body, wherein the YAG layer is substantially free of unreacted yttria, YAP or YAM phases, the method comprising: a) providing an alumina powder comprising alumina particles having a diameter no greater than 23 microns, and wherein 5% to 40% of the alumina particles have a diameter less than 1 micron; c) providing an yttria powder; c) combining the yttria powder and the alumina powder at a molar ratio of yttria to alumina of less than 3:5 to form an yttria and an alumina powder; Aluminum mixture; d) disposing the mixture in a cylindrical volume defined by a tool set of a sintering apparatus to form at least one layer of the mixture, wherein the cylindrical volume has a diameter greater than 100 mm and a vacuum condition is created in the volume; and e) applying uniaxial pressure to the calcined mixture in the cylindrical volume while heating to a sintering temperature and sintering to form a sintered ceramic body including the at least one layer in which yttrium oxide and aluminum oxide particles have been combined with each other to form 99 volume percent or more of polycrystalline yttrium aluminum garnet (YAG).

[0019] Embodiment 9. The method according to Embodiment 8 further includes, before placing the yttrium oxide and aluminum oxide mixture in the cylindrical volume, performing non-reactive calcination of the mixture by raising the temperature to a calcination temperature and maintaining the calcination temperature for a period of time to calcine the mixture.

[0020] Embodiment 10. A method according to Embodiment 8, wherein providing an aluminum oxide powder comprises providing an aluminum oxide powder having a multimodal particle size distribution, wherein the multimodal particle size distribution comprises at least two maxima in particle size.

[0021] Embodiment 11. A method according to Embodiment 8, wherein providing an alumina powder comprises: providing a first alumina powder having particles having a diameter less than 7 microns, the first alumina powder particles comprising a first diameter distribution, the distribution consisting of a single maximum value expressed as a percentage of the amount of the first alumina powder particles, the single maximum value being in a range between 0.2 microns and 0.4 microns; providing a second alumina powder having particles having a diameter less than 11 microns, the second alumina powder particles comprising a second diameter distribution, the distribution including an absolute maximum value expressed as a percentage of the amount of the second alumina powder particles, the absolute maximum value being in a range between 3.4 microns and 4.4 microns; and mixing the first alumina powder and the second alumina powder together in a ratio of 4:1 by weight.

[0022] Embodiment 12. A method according to Embodiment 8, wherein providing an aluminum oxide powder comprises providing an aluminum oxide powder having a multimodal particle size distribution, wherein the multimodal particle size distribution comprises at least three maxima in particle size.

[0023] Embodiment 13. The method of embodiment 9, wherein the first maximum is a particle size between 3 microns and 5.5 microns.

[0024] Embodiment 14. A method according to embodiment 13, wherein the first maximum value is an absolute maximum value expressed as a percentage of the amount of particles.

[0025] Embodiment 15. The method according to Embodiment 9, wherein the second maximum value is 0.7 microns to 1.5 microns.

[0026] Embodiment 16. A method according to Embodiment 9, wherein the ratio of the first maximum value to the second maximum value is in the range between 2:3 and 9:1.

[0027] Embodiment 17. A composition for sintering YAG (yttrium aluminum garnet), the composition comprising a mixture of yttrium oxide and aluminum oxide powders, wherein i) the yttrium oxide powder includes particles falling within a size range between 0 microns and 23 microns; ii) the aluminum oxide powder includes particles falling within a size range between 0 microns and 12 microns; and each of the aluminum oxide powder and the yttrium oxide powder includes a particle size distribution including d50, d10 and d90, wherein the ratio of the d50 of the yttrium oxide powder to the d50 of the aluminum oxide powder falls within a range between 2.64:1 and 6.89:1, the ratio of the d90 of the yttrium oxide powder to the d90 of the aluminum oxide powder falls within a range between 3.4:1 and 17:1, and the ratio of the d10 of the yttrium oxide powder to the d10 of the aluminum oxide powder falls within a range between 1.7:1 and 5:1.

[0028] Embodiment 18. A composition according to Embodiment 17, wherein the aluminum oxide powder further comprises a first maximum and a second maximum of particle size on the aluminum oxide particle size distribution (measured as a percentage of the amount of particle size).

[0029] Embodiment 19. The composition of Embodiment 17, wherein the yttrium oxide powder and the aluminum oxide powder are present in a molar ratio of yttrium oxide to aluminum oxide of less than 3:5.

[0030] Embodiment 20. The composition of Embodiment 17, wherein the yttrium oxide powder and the aluminum oxide powder are present in a molar ratio of yttrium oxide to aluminum oxide of from 3:5 to 3:5.025.

[0031] The embodiments of the present invention may be used alone or in combination with each other. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1is a phase diagram of a two-component yttria / alumina phase diagram, illustrating YAG (Y3Al5O 12 ), Yttrium aluminum oxide phases of YAP (YAlO3) and YAM (Y4Al2O9) and the molar ratios and temperatures required to form them;

[0033] Figure 2 is a graph illustrating a Gaussian particle size curve for a typical commercial sample of yttrium oxide;

[0034] Figure 3 is a particle size distribution graph showing that if the particle distribution of alumina is incorrect, both unreacted alumina and yttrium oxide will be present in the resulting YAG, but if the particle size distribution is correct, only unreacted alumina will be present;

[0035] Figure 4 The particle size distribution of various powders is illustrated in terms of percentage of the amount of particle size;

[0036] Figure 5 Illustrated Figure 4 The particle size distribution as a percentage of the volume of the particles;

[0037] Figure 6 is a SEM micrograph of YAG produced with alumina having only a fine particle distribution, wherein the YAG shows the presence of both unreacted yttrium oxide and alumina (from Figure 4 gray circular samples);

[0038] Figure 7 is a SEM micrograph of YAG produced with alumina having a trimodal particle size distribution, in which only unreacted alumina (from Figure 4 of “good” samples);

[0039] Figure 8 is a SEM micrograph of YAG produced with alumina without fine particles, in which both unreacted alumina and yttrium oxide are visible (from Figure 4 of triangle samples);

[0040] Fig. 9 is a graph illustrating the particle size distribution of a sample of aluminum oxide powder used in Example 2;

[0041] Fig.10 is a SEM micrograph of YAG produced by the process of Example 2;

[0042] Fig.11 is a graph illustrating the particle size distribution of a sample of aluminum oxide powder used in Example 3;

[0043] Fig.12 is a SEM micrograph of YAG produced by the process of Example 3;

[0044] Fig.13 is a graph illustrating the particle size distribution of a sample of aluminum oxide powder used in Example 4;

[0045] Fig.14 is a SEM micrograph of YAG produced by the process of Example 4;

[0046] Fig.15 is a graph illustrating the particle size distribution of a sample of aluminum oxide powder used in Example 5; and

[0047] Fig.16 is a SEM micrograph of YAG produced by the process of Example 5. DETAILED DESCRIPTION

[0048] Reference will now be made in detail to specific embodiments. Although the present disclosure will be described in conjunction with these specific embodiments, it should be understood that this is not intended to limit the present disclosure to these specific embodiments. On the contrary, it is intended to cover alternatives, modifications and equivalents that may be included in the essence and scope defined by the appended claims. In the following description, many specific details are set forth to provide a thorough understanding of the disclosed embodiments. The present disclosure may be practiced without some or all of these specific details.

[0049] Semiconductor etching and deposition reactors require reactor components with surfaces that are highly resistant to corrosion and erosion by halogen-containing plasmas necessary for processing. These surfaces preferably minimize the release of particles from the component surfaces into the chamber. In addition, the chamber components must have sufficient mechanical strength for handling and use, especially when the component sizes are large (diameter>100mm, such as 100mm to 625mm). Sintered ceramic bodies can be machined into sintered components, and therefore, must be able to be handled and machined at large sizes while providing corrosion resistance, low particle generation and high mechanical strength. The sintered ceramic body as disclosed herein includes at least one layer, the at least one layer comprising 90 volume % to 99.8 volume % of polycrystalline yttrium aluminum garnet (YAG), wherein the at least one layer includes at least one surface, and wherein the at least one surface includes pores, the pore size of the pores does not exceed 5μm, and for at least 95% of the pores, the maximum pore size is 1.5μm. These materials have excellent corrosion resistance and erosion resistance. The use of these materials results in semiconductor plasma processing chamber components having surfaces that provide improved plasma resistance compared to other materials when subjected to halogen-based plasma etching and deposition conditions.

[0050] definition

[0051] As used herein, the term "yttrium aluminum oxide" is understood to mean at least one of the crystalline phase forms of yttrium aluminum oxide, including Y3Al5O 12 (YAG; yttrium aluminum garnet / cubic phase), YAlO3 (YAP; yttrium aluminum perovskite phase) and Y4Al2O9 (YAM; yttrium aluminum monoclinic phase) and combinations of these. The terms "YAG" and "YAG phase" are used interchangeably herein.

[0052] As used herein, the term "sintered ceramic body" refers to a single layer or a multilayer body. If a multilayer body, the term refers to a monolithic, unitary sintered ceramic article formed by co-compacting one or more than one powder mixture by applying pressure and heat, which produces a monolithic, dense, multilayer sintered ceramic body. The monolithic, multilayer sintered ceramic body can be machined into a monolithic, multilayer sintered ceramic component that can be used as a chamber component in plasma processing applications. As used herein, the term "co-compacting" refers to a process in which at least two loose powder materials are placed in a mold and subjected to pressure to form a powder compact. The powder compact is free of binders, dispersants, and other similar organic substances required to form green or shaped bodies or tapes as is common in the art.

[0053] "Integral" or "unitary" means a single piece or single one-piece part that is complete in itself without added parts, ie, the part is a one-piece piece formed as a unit with another part.

[0054] The term "substantially" as used in this document is a descriptive term indicating approximation, and means "to a considerable extent" or "to a large extent but not entirely as specified", and is intended to avoid strict numerical boundaries of specified parameters.

[0055] As used herein, the term "sintered ceramic component" or "multilayer sintered ceramic component" refers to a single-layer sintered ceramic body, a multilayer sintered ceramic body, or a corrosion-resistant ceramic after a machining step to form the ceramic into a specific shape for a desired component in a semiconductor processing chamber as disclosed herein.

[0056] As used herein, the term "powder mixture" means one or more starting powders that are mixed together before the sintering process, from which these powders form at least one layer of a multilayer sintered ceramic body after the sintering step.

[0057] The term "annealing" as applied to heat treatment of ceramics is understood herein to mean heat treating the disclosed multi-layer sintered ceramic body in air to relieve stress and / or normalize stoichiometry.

[0058] As used herein, the term "tool set" is a tool set that may include at least a die and at least two punches. When fully assembled, the tool set defines a volume for placing the disclosed powder mixture.

[0059] As used herein, the term "phase" should be understood to mean distinct crystalline regions, portions or layers of a sintered ceramic body having a particular crystal structure.

[0060] As used herein, "solid solution" is defined as a mixture of different elements having the same lattice structure. The mixture within the lattice can be substitutional, where atoms from one starting crystal replace atoms from another starting crystal, or interstitial, where atoms occupy positions that are normally vacant in the lattice.

[0061] As used herein, the term "nanopowder" is intended to encompass nanopowders with a specific surface area greater than 20 m 2 / g of those powders.

[0062] As used herein, the term "phase" should be understood to mean distinct crystalline regions, portions or layers of a sintered ceramic body having a particular crystal structure.

[0063] As used herein, the term "layer" is understood to mean a thickness of material, typically one of several. The material may be, for example, a ceramic powder, a powder mixture, a calcined powder mixture or a sintered region or portion.

[0064] As used herein, "ambient temperature" refers to a temperature range of about 22°C to 25°C.

[0065] As used herein, the term "purity" refers to the absence of various contaminants a) in the starting materials from which the powder mixture may be formed, b) in the processed powder mixture (or calcined powder mixture), and c) in the multilayer sintered ceramic body or component as disclosed herein. Higher purity (approaching 100%) indicates a material that is substantially free of contaminants or impurities, or has very low amounts of contaminants or impurities, and that substantially contains the material composition present in the disclosed starting powder.

[0066] As used herein, the term "impurities" refers to those compounds / contaminants present in a powder or sintered ceramic other than the intended compound itself. Impurities may be present in the starting powder, the powder mixture, the processed powder mixture, and the sintered ceramic body. The impurity content of the powder, the powder mixture, and the first layer and the second layer of the sintered body as disclosed herein was determined using the ICPMS method.

[0067] As used herein, the term "dopant" is a substance added to a bulk material to produce desired properties in a ceramic material (e.g., to change electrical properties). Typically, if used, dopants are present in low concentrations, i.e., >0.002 wt% to <1.0 wt%.

[0068] Impurities differ from dopants in that dopants as defined herein are those compounds intentionally added to the starting powder or powder mixture to achieve certain electrical, mechanical, optical or other properties, such as grain size modification, in the multilayer sintered ceramic body.

[0069] As used herein, the term "sintering aid" refers to compounds that enhance densification and thereby reduce porosity during sintering, such as silicon dioxide (SiO2), lithium oxide (Li2O), lithium fluoride (LiF), magnesium oxide (MgO) and / or calcium oxide (CaO). The Hf and Y present in the starting powder, and the extent to which they remain in the sintered ceramic, do not include sintering aids, impurities or dopants as defined herein.

[0070] As used herein, the terms "about" and "approximately" used in connection with numbers or features as disclosed herein allow for a variance of plus or minus 10%.

[0071] The following detailed description assumes that the present disclosure is implemented in equipment (such as an etching chamber or a deposition chamber) necessary as a part of manufacturing a device on a semiconductor wafer substrate. However, the present invention is not limited to this. The workpiece can have various shapes, sizes and materials. In addition to semiconductor wafer processing, other workpieces that can utilize embodiments of the present invention include various products, such as fine feature size inorganic circuit boards, magnetic recording media, magnetic recording sensors, mirrors, optical elements, micromechanical devices, etc.

[0072] During the processing of semiconductor devices, corrosion resistant parts or chamber components are used within the etch chamber and are exposed to harsh corrosive environments that cause particle release into the etch chamber, resulting in yield loss due to wafer-level contamination. The sintered ceramic bodies and related components disclosed herein provide improved plasma etch resistance and enhanced cleanability within semiconductor processing chambers through specific material properties and features as described below.

[0073] Disclosed herein is a method of preparing a sintered ceramic body comprising at least one layer comprising 90 volume % to 99.8 volume % of polycrystalline yttrium aluminum garnet (YAG), wherein the at least one layer comprises at least one surface, wherein the at least one surface comprises pores having a pore size of no more than 5 μm, and for at least 95% of the pores, the maximum pore size is 1.5 μm. In an embodiment, the sintered ceramic body has a volume porosity of 0.1% to 4%, as calculated by density measurement performed according to ASTM B962-17.

[0074] Preparation method

[0075] The method disclosed herein for preparing a sintered ceramic body includes the following steps: a) combining yttrium oxide powder and aluminum oxide powder to prepare a mixture, wherein i) the yttrium oxide powder is characterized by a particle size distribution, wherein at least 50 volume % of the particles have a size less than 15 microns and the remaining particles have a size between 1 micron and 23 microns, and ii) the aluminum oxide powder is characterized by a particle size distribution, wherein 15% of the particles have a size less than 0.5 microns, 50% of the particles have a size less than 2 microns, and 100% of the particles have a size less than 15 microns; b) disposing the mixture in a volume defined by a tool set of a sintering apparatus to form at least one layer of the mixture and to create a vacuum condition in the volume; c) applying pressure to the at least one layer of the mixture while heating to a sintering temperature and sintering to form a sintered ceramic body, the sintered ceramic body comprising at least one layer, the at least one layer comprising 90 volume % to 99.8 volume % of polycrystalline yttrium aluminum garnet (YAG); and d) reducing the temperature of the sintered ceramic body. The remaining phase consists essentially of unreacted alumina.

[0076] The following additional steps are optional; annealing the ceramic sintered body by applying heat to raise the temperature of the ceramic sintered body to an annealing temperature in an oxidizing, inert, vacuum or reducing atmosphere, depending on the final desired oxidation state of the material, to form an annealed ceramic sintered body; reducing the temperature of the annealed ceramic sintered body; and machining the ceramic sintered body or the annealed ceramic sintered body to produce a ceramic sintered component in an etching chamber, such as a dielectric window or RF window, a focusing ring, a nozzle or a gas injector, a showerhead, a gas distribution plate, an etching chamber liner, a plasma source adapter, a gas inlet adapter, a diffuser, an electronic wafer chuck, a chuck, a disc, a mixing manifold, an ion suppressor element, a panel, an isolator, a spacer and / or a guard ring.

[0077] The preparation of sintered ceramic bodies disclosed herein can be achieved by using pressure-assisted sintering, such as spark plasma sintering (SPS), also known as field-assisted sintering technology (FAST) or direct current sintering (DCS). These direct current sintering and related techniques use direct current to heat an electrically conductive mold structure or tool set to heat the material to be sintered. This heating method allows the application of very high heating and cooling rates, thereby enhancing the densification mechanism rather than the diffusion mechanism that promotes grain growth, which can help to prepare sintered ceramic bodies with very fine grain sizes and transfer the inherent properties of the original powder to a nearly or fully dense product. The direct current pressure-assisted method as disclosed herein utilizes preferably non-pulsed, continuous direct current to heat the disclosed tool set.

[0078] In an embodiment, the method disclosed herein provides the preparation of a ceramic sintered body comprising YAG in a garnet cubic crystal structure in an amount of 90% to 99.5% by volume of the cubic crystal structure, preferably 90% to 99% by volume of the cubic crystal structure, preferably 95% to 99.5% by volume of the cubic crystal structure, preferably 95% to 99% by volume of the cubic crystal structure. In an alternative embodiment, an Al2O3 phase may be present in the ceramic sintered body comprising YAG in an amount of 0.1% to 5% by volume, 0.1% to 3% by volume, 0.1% to 2% by volume, 0.1% to 1% by volume, preferably less than 1% by volume.

[0079] In an embodiment, the disclosed process provides the preparation of highly phase-pure YAG with greater than 99% by volume cubic crystal structure having high (>98%) density, high purity and low porosity. In an alternative embodiment, the disclosed process provides the preparation of highly phase-pure YAG cubic crystal structure with 95% by volume and higher and 5% by volume and lower alumina second crystalline phase, and the sintered body also has high density, high purity and low porosity. In another embodiment, the disclosed process provides yttrium aluminum garnet, Y3Al5O4 with high purity, high density and low porosity. 12 Preparation of mixed phase and / or phase pure ceramic sintered bodies of (YAG), yttrium aluminum perovskite YAlO3 (YAP) and / or yttrium aluminum monoclinic Y4Al2O9 (YAM) and combinations thereof. The disclosed ceramic sintered bodies are particularly suitable for use in plasma processing equipment, such as semiconductor manufacturing equipment. Such parts or components may include windows, nozzles, gas injectors, showerheads, (etching) chamber liners, mixing manifolds, wafer supports, electronic wafer chucks and various rings such as focusing rings and guard rings, as well as other components.

[0080] Using materials and methods as disclosed herein, high densities of the disclosed ceramic sintered bodies, such as 96%, 98%, 99.5% and greater of the theoretical density of phase-pure YAG, can be achieved without the use of sintering aids. Thus, in embodiments, the ceramic sintered body comprising YAG is substantially free of or free of sintering aids (excluding zirconium compounds used as dopants as described herein). In some embodiments, the ceramic sintered body comprising YAG is also substantially free of zirconium compounds.

[0081] In embodiments, a ceramic sintered body comprising 90 volume % to 99.8 volume % polycrystalline YAG may contain excess yttrium oxide and / or alumina over the stoichiometric YAG, which may remain from the process or may be intentionally added during powder batching and preparation. Thus, the excess yttrium oxide and / or alumina are not considered dopants or sintering aids to the extent that they may remain in the ceramic sintered body.

[0082] In another embodiment, the ceramic sintered body comprising 90 volume % to 99.8 volume % polycrystalline YAG may include excess alumina over the stoichiometric YAG, which may be retained from the process or may be intentionally added during powder batching and preparation. In this embodiment, there is no excess yttrium oxide because all of the yttrium oxide is consumed in the YAG forming reaction. In yet another embodiment, yttrium oxide residues remain because all of the alumina is consumed in the YAG forming reaction.

[0083] Step a) of the method disclosed herein comprises combining yttrium oxide powder and aluminum oxide powder to prepare a mixture, wherein i) the yttrium oxide powder is characterized by a particle size distribution, wherein at least 50% by volume of the particles have a size less than 15 microns, and the remaining particles have a size between 1 micron and 23 microns, and ii) the aluminum oxide powder is characterized by a particle size distribution, wherein 15% of the particles have a size less than 0.5 microns, 50% of the particles have a size less than 2 microns, and 100% of the particles have a size less than 15 microns. Thus, the first powder mixture can have a bimodal particle size distribution or a trimodal particle size distribution.

[0084] Figure 2 shows a typical Gaussian particle size distribution for a commercial yttrium oxide powder sample. In contrast, Figure 3 and Figure 4 The particle size distribution of a mixture of yttrium oxide powder and aluminum oxide powder is shown, showing that the above particle size distribution is optimal for ensuring that all yttrium oxide is consumed (see Figure 7 Here, it can be seen that if there are not enough aluminum oxide powder particles smaller than 1 micron, the resulting microstructure will have yttrium oxide present (see Figure 8 If too many alumina particles are less than 1 micron in size, the resulting microstructure will have large areas of alumina present (see Figure 6 SEM micrograph of ). Figure 5 Shows Figure 4 The particle size distribution of the sample is given in volume % of the particle size.

[0085] The starting powder materials of aluminum oxide and yttrium oxide for forming the corrosion-resistant ceramic sintered body and subsequent components including at least one YAG layer are preferably high-purity commercially available powders. d50 is defined as the median value and represents the value at which half of the population is above this point and half is below this point. Similarly, 90% of the distribution is below d90 and 10% of the population is below d10.

[0086] The d10 particle size of the yttrium oxide powder used as a starting material according to one embodiment of the present invention is preferably 1.5 μm to 8.8 μm, preferably 1.7 μm to 7.7 μm, preferably 2.0 μm to 6.7 μm, preferably 2.3 μm to 5.9 μm, preferably 2.6 μm to 5.1 μm, preferably 3.0 μm to 4.5 μm and preferably 3.4 μm to 3.9 μm.

[0087] The d50 particle size of the yttrium oxide powder used as the starting material according to one embodiment of the present invention is preferably 2.3 μm to 17.4 μm, preferably 2.6 μm to 15.2 μm, preferably 3 μm to 13.2 μm, preferably 3.4 μm to 11.6 μm, preferably 3.9 μm to 10.1 μm, preferably 4.5 μm to 8.8 μm, preferably 5.1 μm to 7.7 μm and preferably 5.9 μm to 6.7 μm.

[0088] The d90 particle size of the yttrium oxide powder used as the starting material according to one embodiment of the present invention is preferably 4.5 μm to 19.9 μm, preferably 5.1 μm to 17.4 μm, preferably 5.9 μm to 15.2 μm, preferably 6.7 μm to 13.2 μm, preferably 10 μm to 20 μm, preferably 7.7 μm to 11.6 μm, preferably 8.8 μm to 10.1 μm and preferably 10 μm to 18 μm.

[0089] The yttrium oxide powder preferably has a 0.75 m 2 / g to 12m 2 / g, preferably 0.75m 2 / g to 10m 2 / g, preferably 0.75m 2 / g to 8m 2 / g, preferably 0.75m 2 / g to 6m 2 / g, preferably 0.75m 2 / g to 4m 2 / g, preferably 0.75m 2 / g to 2m 2 / g, preferably 1m 2 / g to 6m 2 / g, preferably 1m 2 / g to 4m 2 / g, preferably 2m 2 / g to 10m 2 / g, preferably 4m 2 / g to 10m 2 / g, preferably 6m 2 / g to 10m 2 / g, and preferably 1m2 / g to 4m 2 / g specific surface area (SSA).

[0090] The purity of the yttrium oxide starting material is preferably above 99.99%, preferably above 99.995%, preferably above 99.999%, more preferably above 99.9995%, and more preferably above 99.9999%, as measured by fully acid digested powder and ICP-MS. This corresponds to an impurity content of 100 ppm and less, preferably 50 ppm and less, preferably 25 ppm and less, preferably 10 ppm and less, more preferably about 1 ppm, preferably 1 ppm to 100 ppm, preferably 1 ppm to 50 ppm, preferably 1 ppm to 25 ppm, preferably 1 ppm to 10 ppm, and preferably 1 ppm to 5 ppm.

[0091] The d10 particle size of the aluminum oxide powder used as a starting material according to one embodiment of the present invention is preferably 0.05 μm to 3.0 μm, preferably 0.05 μm to 2.6 μm, preferably 0.05 μm to 2.3 μm, preferably 0.05 μm to 2 μm, preferably 0.05 μm to 0.75 μm, preferably 0.05 μm to 1.7 μm, preferably 0.12 μm to 1.5 μm, preferably 0.12 μm to 1.3 μm, preferably 0. .12μm to 1.2μm, preferably 0.12μm to 1μm, preferably 0.13μm to 0.88μm, preferably 0.15μm to 0.77μm, preferably 0.17μm to 0.67μm, preferably 0.20μm to 0.67μm, preferably 0.23μm to 0.58μm, preferably 0.26μm to 0.51μm, preferably 0.30μm to 0.45μm and preferably 0.34μm to 0.39μm.

[0092] The d50 particle size of the aluminum oxide powder used as starting material according to one embodiment is typically 0.39 μm to 11.6 μm, preferably 0.45 μm to 10.1 μm, preferably 0.51 μm to 8.8 μm, preferably 0.58 μm to 1 μm, preferably 0.67 μm to 6.7 μm, preferably 0.77 μm to 5.9 μm, preferably 0.88 μm to 5.1 μm, preferably 1.0 μm to 4.5 μm, preferably 1.2 μm to 3.9 μm, preferably 1.3 μm to 3.4 μm, preferably 1.5 μm to 3.0 μm, preferably 1.7 μm to 2.6 μm and preferably 2.0 μm to 2.3 μm.

[0093] The d90 particle size of the aluminum oxide powder used as a starting material according to one embodiment of the present invention is 0.58 μm to 67.5 μm, preferably 0.67 μm to 59.0 μm, preferably 0.77 μm to 51.5 μm, preferably 0.88 μm to 44.9 μm, preferably 1.0 μm to 39.2 μm, preferably 1.2 μm to 34.3 μm, preferably 1.3 μm to 29.9 μm, preferably 1.5 μm to 26.1 μm. m, preferably 1.7μm to 22.8μm, preferably 2.0μm to 19.9μm, preferably 2.3μm to 17.4μm, preferably 2.6μm to 15.2μm, preferably 3.0μm to 13.2μm, preferably 3.4μm to 11.6μm, preferably 3.9μm to 10.1μm, preferably 4.5μm to 8.8μm, preferably 5.1μm to 7.7μm, preferably 5.9μm to 6.7μm.

[0094] Alumina powder usually has 3m 2 / g to 18m 2 / g, preferably 3m 2 / g to 16m 2 / g, preferably 3m 2 / g to 14m 2 / g, preferably 3m 2 / g to 12m 2 / g, preferably 3m 2 / g to 10m 2 / g, preferably 3m 2 / g to 6m 2 / g, preferably 6m 2 / g to 18m 2 / g, preferably 6m 2 / g to 14m 2 / g, preferably 8m 2 / g to 18m 2 / g, preferably 10m 2 / g to 18m 2 / g, preferably 8m 2 / g to 10m 2 / g, preferably 4m 2 / g to 9m 2 / g, preferably 5m 2 / g to 10m 2 / g and preferably 6m 2 / g to 9m 2 / g specific surface area.

[0095] As measured using the ICPMS method, the purity of the alumina starting material is typically above 99.99%, preferably above 99.995%, preferably above 99.999% and preferably above 99.9995%. Accordingly, the impurity content of the alumina powder may be 100 ppm and less, preferably 50 ppm and less, preferably 25 ppm and less, preferably 10 ppm and less and more preferably 5 ppm and less.

[0096] In an embodiment, the alumina powder may include 80 to 100 volume % of the α alumina crystalline phase, preferably 90 to 100 volume % of the α alumina crystalline phase, and preferably 95 to 100 volume % of the α alumina crystalline phase.

[0097] Table 1 lists the properties of the disclosed starting materials for forming the sintered bodies comprising YAG. The particle sizes of the starting powders, powder mixtures, and calcined powder mixtures were measured using a Horiba Model LA-960 Laser Scattering Particle Size Distribution Analyzer capable of measuring particle sizes from 10 nm to 5 mm. The specific surface areas of the starting powders, powder mixtures, and calcined powder mixtures were measured using a Horiba BET Surface Area Analyzer Model SA-9601 capable of measuring particle sizes from 0.01 nm to 5 mm. 2 / g to 2000m 2 The specific surface area of ​​​​the sample can be measured in grams, with an accuracy of 10% or less for most samples.

[0098] Table 1

[0099] d10(um) d50(um) d90(um) SSA(m2 / g) Yttrium Oxide 1 to 7 3 to 11 6 to 20 0.75 to 12 Alumina 0.05 to 4 0.15 to 8 0.50 to 75 3 to 18

[0100] In one embodiment, a dopant including a zirconium compound is added to yttrium oxide and aluminum oxide powder. Once the YAG layer is formed and irradiated with UV light, zirconium oxide plays a role in giving the YAG layer a red color. The zirconium compound includes, for example, zirconium oxide (zirconium oxide), zirconium chloride, zirconium nitrate or any other counter ion of zirconium. In a preferred embodiment, zirconium is added as zirconium oxide oxide, and zirconium oxide can be stabilized with, for example, yttrium oxide. The amount of the dopant zirconium compound should be sufficient to deliver an amount of 15ppm to 500ppm, 15ppm to 350ppm, 15ppm to 250ppm, 15ppm to 200ppm, 15ppm to 100ppm, 15ppm to 50ppm, 50ppm to 225ppm, 50ppm to 200ppm, 50ppm to 175ppm, 50ppm to 150ppm, 50ppm to 150ppm, 50ppm to 125ppm, 50ppm to 100ppm and 50ppm to 75ppm of zirconium.

[0101] For embodiments in which the zirconium dopant compound is zirconium oxide, the zirconium oxide powder may have a particle size distribution with a d10 of 0.08 μm to 0.20 μm, a d50 of 0.3 μm to 0.7 μm, and a d90 of 0.9 μm to 5 μm. The average particle size of the zirconium oxide powder used as a starting material for a mixture according to an embodiment of the present invention may be 0.3 μm to 1 μm.

[0102] Zirconia powders typically have a 1 m 2 / g to 16m 2 / g, preferably 2m 2 / g to 14m 2 / g, preferably 4m 2 / g to 12m 2 / g and more preferably 5m 2 / g to 9m 2 / g specific surface area (SSA).

[0103] The purity of the zirconium oxide powder starting material (if used) is preferably above 99.8%, preferably above 99.9%, preferably above 99.95%, preferably above 99.975%, preferably above 99.99% and preferably above 99.995%. This corresponds to a total impurity content of 2000 pm and less, preferably 1000 ppm and less, preferably 500 ppm and less, preferably 250 ppm and less, preferably 100 ppm and less, preferably 50 ppm and less and preferably 25 ppm to 150 ppm as measured using the ICPMS (Inductively Coupled Plasma Mass Spectrometry) method disclosed herein. As is common in many commercially available zirconium oxide powders, the zirconium oxide used in the embodiments disclosed herein typically contains a low amount of Hf of about 2 wt% to 5 wt%.

[0104] In other embodiments, it may be preferred that the first powder mixture does not contain a specific surface area of ​​about 2 m 2 / g and greater YAG phase to form at least a first layer of a multi-layer sintered ceramic body comprising YAG by an in-situ, reactive phase sintering process as disclosed herein. All purity measurements disclosed herein are measured above the reporting limit of the specific element and are completed using ICPMS from an Agilent 7900 ICP-MS Model G8403, a quadrupole mass spectrometry system. The detection limits for identifying the presence of lighter elements using the ICP-MS method as disclosed herein are higher than the reporting limits for heavier elements.

[0105] In an embodiment, a sintered ceramic body comprising 90% to 99.8% by volume of polycrystalline yttrium aluminum garnet (YAG) may be formed from a stoichiometric powder mixture of 37.5 mol% yttrium oxide and 62.5 mol% aluminum oxide. 12 Mechanisms of nonstoichiometry in Y3Al5O 12 )", Patel et al., 2008, Appl. Phys. Lett. 93, 191902 (2008) showed that the width of the phase domain can have a variation of 0.1 mol% and less. Therefore, deviations of 0.1 mol% and less from the stoichiometric YAG (37.5% alumina / 62.5% yttrium oxide) may result in the formation of phase-pure yttrium aluminum oxide garnet. Therefore, in embodiments, the yttrium aluminum garnet (YAG) garnet cubic phase (Y3Al5O 12 ) can be formed from starting powders combined into a powder mixture at a ratio of 37.4 mol% to 37.6 mol% yttrium oxide and 62.6 mol% and 62.4 mol% aluminum oxide. The powder mixture can be formed from about 42.9% to 43.4% aluminum oxide and 57.1% to 56.6% yttrium oxide by weight.

[0106] Combining the above-described starting powders including yttrium oxide and aluminum oxide having the particle size distribution disclosed above can be performed using powder preparation techniques of wet or dry ball milling (axial rotation), wet or dry tumbling (upside down or vertical) mixing, and combinations of these.

[0107] In order to maintain the purity of the starting powder during mixing, high purity (>99.99%) alumina media can be used to complete ball milling or upside-down tumbling mixing under dry conditions. The high purity alumina media used in this article was tested using the ICPMS method, and its purity was found to be 99.997%. The media load for dry ball or tumbling mixing can vary between large size (about 30mm) media elements to about 50% of the media load by weight of the powder. Dry milling or mixing can be carried out for a duration of 12 hours to 48 hours, preferably 16 hours to 48 hours, preferably 24 hours to 48 hours using an RPM of 50RPM to 200RPM, preferably 75RPM to 150RPM, preferably 100RPM to 125RPM.

[0108] Wet ball milling or tumbling mixing can be performed by suspending the starting powder in various solvents such as ethanol, methanol and other alcohols and / or water to form a slurry. The slurry can be formed to have a powder loading of 5% to 50% by weight of the powder, preferably 10% to 40% by weight of the powder, preferably 20% to 40% by weight of the powder during grinding or mixing. Wet mixing or grinding improves the dispersion of the powder by increasing fluidity, thereby producing a fine-scale, uniform mixing before heat treatment or calcination. In a particular embodiment, a dispersant can be optionally added to the slurry using many commercially available dispersants (e.g., polymethyl methacrylate (PMMA) and polyvinyl pyrrolidone (PVP)). The dispersant can optionally be added in an amount of zero (no dispersant) to 0.2% by weight of the powder, preferably 0% to 0.1% by weight of the powder. The media loading can vary from no media used during grinding to 50% and higher by weight of the powder, preferably 40% to 100% by weight of the powder, preferably 60% to 100% by weight of the powder, preferably 50% to 80% by weight of the powder. Wet ball milling or tumbling mixing can be performed for a duration of 8 hours to 48 hours, preferably 12 hours to 48 hours, preferably 16 hours to 48 hours, preferably 8 hours to 36 hours, preferably 8 hours to 24 hours, preferably 8 hours to 12 hours. For a container of up to about 200 mm in diameter, ball milling can use an RPM of 50RPM to 200RPM, preferably 75RPM to 150RPM, preferably 100RPM to 125RPM. Upside-down tumbling mixing can be performed at an RPM of 10rpm to 30rpm, preferably about 20rpm.

[0109] The jet milling process known to those skilled in the art can also be used to thoroughly mix powders to form powders, powder mixtures or calcined powder mixtures with narrow particle size distribution. Jet milling uses a high-speed jet of an inert gas or air to collide particles of a starting powder and / or a powder mixture and / or a calcined powder mixture without using a grinding or mixing medium, thereby maintaining the initial purity of the powder to be milled. Starting powders, powder mixtures and / or calcined powder mixtures as disclosed herein can be jet milled at a pressure of about 100 psi, either alone or in combination with any or all of the powder milling / mixing methods disclosed herein. After jet milling, the powder or powder mixture can be optionally sieved using any number of screens that can have, for example, an opening of 45 μm to 400 μm, and blended, but not limited to repetition or sequence.

[0110] The use of wet ball milling, tumbling mixing and / or jet milling is a high energy process that breaks down particles and agglomerates, improves dispersion by increased particle mobility, and can provide fine-scale mixing, thereby providing a uniform powder mixture before calcining. Additional powder preparation processes of milling, high shear mixing, planetary grinding, and other processes known to those skilled in the art can also be applied. The slurry can be dried by a rotary evaporation method. In other embodiments, spray drying techniques known in the art can be used to dry the slurry. Before or after drying, a screen with an opening of, for example, 35 μm to 75 μm can be used to screen the powder mixture. The above-mentioned powder preparation techniques can be used alone or in any combination thereof.

[0111] After drying, the surface area of ​​the powder mixture of step a) may be 2 m 2 / g to 17m 2 / g, 2m 2 / g to 14m 2 / g, 2m 2 / g to 12m 2 / g, 2m 2 / g to 10m 2 / g, 4m 2 / g to 17m 2 / g, 6m 2 / g to 17m 2 / g, 8m 2 / g to 17m 2 / g, 10m 2 / g to 17m 2 / g, 4m 2 / g to 12m 2 / g, 4m 2 / g to 10m 2 / g, and 5m 2 / g to 8m 2 / g.

[0112] At this point, if a multilayer sintered ceramic body is to be formed, a second powder mixture is formed. The second powder mixture may include, for example, combining alumina powder and zirconia powder, wherein the zirconia powder includes at least one of partially stabilized and stabilized zirconia powders to prepare a second powder mixture as described in U.S. Patent Application Serial No. 63 / 216,356 filed on June 29, 2021, the contents of which are incorporated herein by reference.

[0113] In an optional step, the methods disclosed herein may include the step of heating the first powder mixture (and any additional powder mixtures) to a calcination temperature and maintaining the calcination temperature for a certain duration to form a first calcined powder mixture (also referred to herein as "calcined powder mixture"). Calcination as disclosed herein may be performed in an oxygen-containing environment at ambient pressure, although other pressures and calcination environments may be used.

[0114] Before sintering, calcination can be performed to remove moisture and ensure that the surface state of the powder mixture is uniform. In certain embodiments, calcination can be performed to reduce the surface area. In other embodiments, calcination does not result in a reduction in the surface area of ​​the starting powder.

[0115] The calcination according to the heat treatment step may be carried out at a temperature of 600°C to 1100°C, preferably 600°C to 1000°C, preferably 600°C to 900°C, preferably 700°C to 1100°C, preferably 800°C to 1100°C, preferably 800°C to 1000°C, and preferably 850°C to 950°C. The calcination may be carried out in an oxygen-containing environment for a duration of 4 hours to 12 hours, preferably 4 hours to 10 hours, preferably 4 hours to 8 hours, preferably 6 hours to 12 hours, preferably 4 hours to 6 hours. After calcination, the calcined powder mixture may be sieved, for example, through a mesh screen having 45 μm to 400 μm openings, and / or tumbled and / or blended according to known methods to form a calcined powder mixture.

[0116] The calcined powder mixture to form the YAG phase may have a d10 particle size of preferably 0.06 μm to 4 μm, preferably 0.08 μm to 4 μm, preferably 0.1 μm to 4 μm, preferably 0.2 μm to 4 μm, preferably 0.3 μm to 4 μm, preferably 0.4 μm to 4 μm, preferably 0.08 μm to 3 μm, preferably 0.08 μm to 2 μm, preferably 0.08 μm to 1 μm, preferably 0.5 μm to 3 μm, preferably 1 μm to 2 μm and preferably 1 μm to 3 μm.

[0117] The d50 particle size of the calcined powder mixture can vary between 0.7 μm and 50 μm, preferably 1 μm to 40 μm, preferably 1 μm to 30 μm, preferably 1 μm to 20 μm, preferably 1 μm to 10 μm, preferably 1 μm to 5 μm, preferably 5 μm to 50 μm, preferably 10 μm to 50 μm, preferably 20 μm to 50 μm, preferably 30 μm to 50 μm, preferably 3 μm to 8 μm, preferably 5 μm to 10 μm and preferably 6 μm to 15 μm.

[0118] The d90 particle size of the calcined powder mixture may be preferably 10 μm to 350 μm, preferably 10 μm to 300 μm, preferably 10 μm to 250 μm, preferably 10 μm to 200 μm, preferably 10 μm to 175 μm, preferably 10 μm to 150 μm, preferably 10 μm to 100 μm, preferably 10 μm to 75 μm, preferably 10 μm to 50 μm, preferably 10 μm to 40 μm, preferably 10 μm to 50 μm. 30μm, preferably 15μm to 45μm, preferably 20μm to 40μm, preferably 20μm to 350μm, preferably 40μm to 350μm, preferably 60μm to 350μm, preferably 100μm to 350μm, preferably 150μm to 350μm, preferably 200μm to 350μm, preferably 12μm to 330μm, preferably 100μm to 330μm and preferably 100μm to 250μm.

[0119] In certain embodiments, the calcination conditions as disclosed herein may result in the formation of one or more crystalline phases of the crystalline phases of YAP, YAM and YAG and their combinations, and / or the agglomeration of the powder mixture, and thus may result in a wide range of particle or agglomerate sizes. Therefore, in some embodiments, the particle size referred to herein may include a single particle, and in other embodiments, the particle size referred to herein may include an agglomerate containing more than one particle or an agglomerate of multiple particles, which can be measured as a single large particle using a laser particle size detection method as disclosed herein. The particles including either or both of the agglomerates of a single particle or multiple particles may include at least one crystalline phase selected from the group consisting of: yttrium oxide, aluminum oxide, yttrium aluminum perovskite (YAP), yttrium aluminum monoclinic (YAM) and YAG (garnet) phases and their combinations. In other embodiments, the calcination conditions at lower temperatures as disclosed herein may not affect the particle size distribution relative to the starting material, and the particle size distribution is within the same or similar range as the starting powder material. The management of batch-to-batch variation and heat transfer during calcination can also contribute to the broadened particle size distribution. The starting powder, powder mixture, and / or calcined powder mixture as disclosed herein can be subjected to any one or combination of the mixing / grinding processes as disclosed herein. Thus, a wide range of particle size distributions can be produced by the calcination conditions and processes as disclosed herein.

[0120] The calcined powder mixture may have a particle size of about 1 m 2 / g to about 18m 2 / g, preferably about 1m 2 / g to about 14m 2 / g, preferably about 1m 2 / g to about 10m 2 / g, preferably about 1m 2 / g to about 8m 2 / g, preferably about 2m 2 / g to about 18m 2 / g, preferably about 2m 2 / g to about 14m 2 / g, preferably about 2m 2 / g to about 10m 2 / g, preferably about 3m 2 / g to about 9m 2 / g, preferably about 3m 2 / g to about 6m 2 / g specific surface area (SSA).

[0121] The calcined powder mixture may have a total impurity content of 5 ppm to 200 ppm, preferably 5 ppm to 150 ppm, preferably less than 100 ppm, preferably less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably 10 ppm to 100 ppm, preferably 10 ppm to 80 ppm, preferably 10 ppm to 60 ppm, preferably 10 ppm to 40 ppm, preferably 20 ppm to 80 ppm, and preferably 30 ppm to 60 ppm, relative to the mass of the calcined powder mixture.

[0122] Table 2 shows the ICPMS purity results of a typical calcined powder mixture prior to formation into a polycrystalline YAG layer according to the present disclosure.

[0123] Table 2

[0124]

[0125]

[0126] *N / A indicates the elements present in the starting powders forming the powder mixture.

[0127] In one embodiment, the sintered ceramic body comprises polycrystalline yttrium aluminum garnet having an impurity of 50 ppm or less of trace metals Na, Fe, and Mg as determined by ICPMS. In another embodiment, the sintered ceramic body comprises polycrystalline yttrium aluminum garnet having an impurity of 50 ppm or less of trace metals Na, Fe, and Mg as determined by ICPMS. In yet another embodiment, the sintered ceramic body comprises polycrystalline yttrium aluminum garnet having a purity of 50 ppm or less of trace elements Li, Na, Mg, K, Ca, B, P, Fe, Cu, Cr, Zn, In, Sn, and Sb (total) as determined by ICPMS.

[0128] Step b) of the method disclosed herein comprises placing the powder mixture (including the calcined powder mixture, if the calcination step is performed) in a volume defined by a tool set of a sintering apparatus to form at least one layer of the mixture and creating a vacuum condition in the volume. The spark plasma sintering (SPS) apparatus used in the process as disclosed herein comprises at least one graphite mold, which is typically a cylindrical graphite mold. In the graphite mold, the first powder mixture (or the first calcined powder mixture) is placed between two graphite punches. In an embodiment in which a multilayer sintered ceramic body is formed, the calcined powder mixture is added sequentially to correspond to the desired sintered material layers.

[0129] In some embodiments, yttrium oxide powder and alumina powder are combined in a molar ratio of yttrium oxide to alumina of less than 5:3 to form a mixture. This ratio promotes reaction during sintering and particle size distribution so that substantially all or all of the yttrium oxide reacts during sintering. Therefore, also disclosed herein is a method for producing a YAG layer of less than 1% alumina-rich in a sintered ceramic body, in which the YAG layer is substantially free of unreacted yttrium oxide, YAP and YAM, the method comprising: (a) providing an alumina powder comprising alumina particles having a diameter not greater than 10 microns, and wherein less than 40% of the alumina particles have a diameter less than 1 micron; (b) providing yttrium oxide powder; (c) combining the yttrium oxide powder and the alumina powder in a molar ratio of yttrium oxide to alumina of less than 5:3 to form a yttrium oxide and alumina mixture; (d) by increasing the temperature to a calcination temperature and maintaining the calcination temperature for a period of time (e) placing the calcined mixture in a cylindrical volume defined by a tool set of a sintering apparatus to form at least one layer of the calcined mixture, wherein the cylindrical volume has a diameter greater than 100 mm and a vacuum condition is created within the volume; and (f) applying uniaxial pressure to the calcined mixture in the cylindrical volume while heating to a sintering temperature and sintering to form a sintered ceramic body comprising the at least one layer, wherein the yttrium oxide and aluminum oxide particles have been combined with each other to form 99 volume % or more of polycrystalline yttrium aluminum garnet (YAG) in the at least one layer.

[0130] In a preferred embodiment, the SPS tool comprises a die including a sidewall including an inner wall and an outer wall, wherein the inner wall has a diameter defining an internal volume capable of receiving at least one ceramic powder; and an upper punch and a lower punch operably connected to the die, wherein each of the upper punch and the lower punch has an outer wall, the diameter defined by the outer wall being smaller than the diameter of the inner wall of the die, thereby defining a gap between each of the upper punch and the lower punch and the inner wall of the die when at least one of the upper punch and the lower punch moves within the internal volume of the die, wherein the gap is 10 μm to 100 μm wide. In some embodiments, the gap is 10 μm to 70 μm wide. Preferably, the die and the punch are made of graphite. Such SPS tools are disclosed in U.S. Provisional Patent Application Serial No. 63 / 087,204 filed on October 3, 2020, which is incorporated herein by reference.

[0131] In an embodiment, one or more (for multi-layer embodiments) calcined powder mixtures may be placed in a graphite mold (sequentially for multi-layer embodiments). Vacuum conditions as known to those skilled in the art are established within the powder between the punches surrounded by the mold. Typical vacuum conditions include 10 -2 Support up to 10 -3 The pressure of torr. The vacuum is applied primarily to remove air to prevent the graphite from burning and to remove most of the air from the powder mixture. In multilayer embodiments, the order in which the powder mixture is placed can be reversed or repeated as needed to achieve the desired structure of the multilayer sintered ceramic body and the parts formed therefrom. In such embodiments, the multilayer first calcined powder mixture and the second calcined powder mixture are adjacent when placed in the graphite mold during sintering, and are then sintered to form a first adjacent layer and a second adjacent layer.

[0132] Step c) of the method disclosed herein comprises applying pressure to at least one layer of the mixture while heating to a sintering temperature and sintering to form a sintered ceramic body comprising at least one layer comprising 90 volume % to 99.8 volume % of polycrystalline yttrium aluminum garnet (YAG), and step d) comprises reducing the temperature of the sintered ceramic body by, for example, removing or shutting down a heat source of the sintering equipment to cool the ceramic sintered body.

[0133] Pressure may be applied to the powder mixture disposed between the graphite punches and increased to a pressure of 5 to 100 MPa, preferably 5 to 60 MPa, preferably 5 to 40 MPa, preferably 5 to 20 MPa, preferably 5 to 15 MPa, preferably 10 to 60 MPa, preferably 10 to 40 MPa, preferably 10 to 30 MPa, preferably 10 to 20 MPa, preferably 13 to 18 MPa, preferably 15 to 60 MPa, preferably 15 to 40 MPa, preferably 15 to 30 MPa, and preferably 20 to 40 MPa. Pressure is applied axially to the powder mixture in the die.

[0134] In a preferred embodiment, the powder mixture is heated directly by the punch and die of the sintering device. The die may contain a conductive material such as graphite, which facilitates resistive / joule heating. The temperature of the sintering device according to the present invention is usually measured in the graphite die of the device. Therefore, it is preferred to measure the temperature as close as possible to the processed calcined powder mixture so that the indicated temperature is actually achieved in the calcined powder mixture to be sintered.

[0135] Applying heat to the calcined powder mixture and / or layered powder mixture arranged in the mold is advantageous to achieve the following sintering temperature: 1000°C to 1700°C, preferably 1200°C to 1700°C, preferably 1400°C to 1700°C, preferably 1500°C to 1700°C, more preferably 1600°C to 1700°C, preferably 1200°C to 1600°C, preferably 1200°C to 1400°C, preferably 1400°C to 1600°C, preferably 1500°C to 1600°C. Sintering can generally be achieved with an isothermal time of 0.5 to 180 minutes, preferably 0.5 to 120 minutes, preferably 0.5 to 100 minutes, preferably 0.5 to 80 minutes, preferably 0.5 to 60 minutes, preferably 0.5 to 40 minutes, preferably 0.5 to 20 minutes, preferably 0.5 to 10 minutes, preferably 0.5 to 5 minutes, preferably 5 to 120 minutes, preferably 10 to 120 minutes, preferably 20 to 120 minutes, preferably 40 to 120 minutes, preferably 60 to 120 minutes, preferably 80 to 100 minutes, preferably 100 to 120 minutes, preferably 30 to 60 minutes, preferably 15 to 45 minutes. In certain embodiments, sintering can be achieved with an isothermal time of zero, and when the sintering temperature is reached, a cooling rate as disclosed herein is initiated. During sintering, a volume reduction typically occurs such that the volume of the ceramic sintered body may be approximately one-third of the volume of the starting powders disposed in the tool set of the sintering apparatus. Through the combined properties of the particle size distribution, purity and / or surface area of ​​the powder mixture as disclosed herein, polycrystalline YAG is preferably formed in situ by reactive sintering during the sintering step.

[0136] In one embodiment, the order in which pressure and temperature are applied may vary according to the present disclosure, meaning that the indicated pressure may be applied first and then heat may be applied to reach the desired temperature. Furthermore, in other embodiments, the indicated heat may also be applied first to reach the desired temperature and the indicated pressure may be applied thereafter. In a third embodiment according to the present disclosure, temperature and pressure may be applied simultaneously to the calcined powder mixture to be sintered and increased until the indicated values ​​are reached.

[0137] Induction or radiation heating methods can also be used to heat the sintering equipment and indirectly heat the calcined powder mixture in the tool set.

[0138] Compared to other sintering techniques, sintering aids are not required (although they can be used if desired). In addition, high purity starting powders are ideal for optimal etching performance. As disclosed herein, the lack of sintering aids and the use of high purity starting materials with a purity of 99.99% to about 99.9999% enable the manufacture of high purity, high density / low porosity ceramic sintered bodies that provide improved etch resistance for use as ceramic sintered components in semiconductor etching chambers.

[0139] In one embodiment of the present invention, process step c) may further include a pre-sintering step having a specific temperature ramp rate of 0.1°C / min to 100°C / min, 0.1°C / min to 50°C / min, 0.1°C / min to 25°C / min, preferably 0.5°C / min to 50°C / min, preferably 0.5°C / min to 25°C / min, preferably 0.5°C / min to 10°C / min, preferably 0.5°C / min to 5°C / min, preferably 0.75°C / min to 25°C / min, preferably 1°C / min to 10°C / min, preferably 1°C / min to 5°C / min, until a specific pre-sintering time is reached.

[0140] In another embodiment of the present invention, process step c) may further include a pre-sintering step with a specific pressurization slope of 0.50 MPa / min to 30 MPa / min, preferably 0.75 MPa / min to 20 MPa / min, more preferably 1 MPa / min to 10 MPa / min, until a specific pre-sintering time is reached.

[0141] At the end of process step c), the method further comprises step d), under vacuum conditions known to those skilled in the art, the temperature of the sintered ceramic body is reduced according to the natural cooling (non-forced cooling) of the processing chamber. In another embodiment according to process step d), the ceramic sintered body can be cooled under inert gas convection, for example under 1 bar of argon or nitrogen. Other gas pressures greater than or less than 1 bar can also be used. In another embodiment, the ceramic sintered body is cooled in an oxygen environment under forced convection conditions. To start the cooling step, at the end of sintering step d, the power applied to the sintering device is removed, and the pressure applied to the ceramic sintered body is removed, and then cooled according to step d). The cooling rate of the ceramic sintered body as disclosed herein can be 0.5°C / min to 20°C / min, 1°C / min to 10°C / min, preferably 1°C / min to 8°C / min, preferably 1°C / min to 5°C / min, preferably 2°C / min to 10°C / min, preferably 2°C / min to 8°C / min, preferably 2°C / min to 5°C / min.

[0142] Optionally but preferably, the method as disclosed herein comprises the steps of: annealing the sintered ceramic body (or a part formed therefrom) by applying heat to raise the temperature of the sintered ceramic body to an annealing temperature for annealing; and reducing the temperature of the annealed sintered ceramic body (or a part formed therefrom). In the optional annealing step according to the embodiments as disclosed herein, the multilayer sintered ceramic body may be subjected to a temperature of about 900°C to about 1800°C, preferably about 1250°C to about 1700°C, preferably about 1300°C to about 1650°C, and preferably about 1400°C to about 1600°C.

[0143] In an embodiment, the optional annealing of the sintered ceramic body can be carried out at a heating rate and / or cooling rate of 0.5°C / min to 50°C / min, preferably 0.5°C / min to 25°C / min, more preferably 0.5°C / min to 10°C / min, and more preferably 0.5°C / min to 5°C / min, more preferably 1°C / min to 50°C / min, more preferably 3°C / min to 50°C / min, more preferably 5°C / min to 50°C / min, more preferably 25°C / min to 50°C / min, preferably 1°C / min to 10°C / min, preferably 2°C / min to 10°C / min, and preferably 2°C / min to 5°C / min.

[0144] The duration of the optional annealing step may be from 1 hour to 24 hours, preferably from 1 hour to 18 hours, preferably from 1 hour to 16 hours, preferably from 1 hour to 8 hours, preferably from 4 hours to 24 hours, preferably from 8 hours to 24 hours, preferably from 12 hours to 24 hours, preferably from 4 hours to 12 hours and preferably from 6 hours to 10 hours.

[0145] In one embodiment, an optional annealing according to the present disclosure may be performed in a sintering apparatus after the sintering process. The optional annealing process may preferably be performed under oxidizing conditions such as forced convection or in air. Annealing results in a refinement of the chemical and physical properties of the sintered ceramic body or a component made therefrom by reducing oxygen vacancies for stoichiometric correction and reducing stress in the sintered body or component. The optional process step of annealing the corrosion-resistant sintered component is performed in an oxidizing atmosphere, whereby the annealing process can provide increased reflectivity, improved mechanical handling, and reduced porosity. After performing the optional process step of annealing the multilayer sintered ceramic body, the temperature of the sintered ceramic body (and in some cases the annealed multilayer sintered ceramic body) is reduced to ambient temperature by removing the heat source.

[0146] In embodiments where a zirconium compound is added as a dopant to the first powder mixture to impart a uniform color to the layer, the methods disclosed herein include an optional step of exposing the sintered ceramic body to UV radiation for a period of time of from 1 minute to 400 minutes. The purpose of the UV exposure step is to activate the doped zirconium to impart a red color to the sintered ceramic body. The length of time for UV radiation exposure should be determined by the uniformity and intensity of the red color imparted to the sintered ceramic body. The total exposure time will depend on the intensity of the UV lamp used to irradiate the sintered ceramic body.

[0147] In a preferred embodiment, the UV light is provided by a UV lamp, such as a Heraeus Noblelight Hammer Mark IIIH10 lamp system, using H + The bulb and R500 reflector delivered UV radiation at a distance of 3 inches from the sintered ceramic body for an exposure period of approximately 6 hours.

[0148] The above process is suitable for producing sintered ceramic bodies as disclosed herein, whose maximum dimensions are, for example, 100 mm to about 625 mm, preferably 100 mm to 622 mm, preferably 200 mm to about 625 mm, preferably 300 mm to about 625 mm, preferably 400 mm to about 625 mm, preferably 500 mm to about 625 mm, preferably 300 mm to 622 mm, preferably 400 mm to 622 mm, and preferably 500 mm to 622 mm. Despite the large size, the sintered ceramic bodies produced according to the method disclosed herein have a uniform density of up to 99.5% of the theoretical value of YAG. The sintered ceramic bodies are formed into, for example, a disk shape with a diameter as the maximum dimension. The disclosed process provides rapid powder consolidation and densification, maintains a maximum grain size of about 10 μm and less in the sintered ceramic body, and achieves high density and low porosity in at least one first layer over the maximum dimension. This combination of fine grain size, high density, and CTE matching provides a large-scale, high-strength sintered ceramic body that is suitable for machining, handling, and use as a component in a semiconductor plasma processing chamber.

[0149] The method as disclosed herein may optionally include the step of machining the sintered ceramic body (or annealed sintered ceramic body) to form sintered ceramic parts in the shape of windows, covers, dielectric windows, RF windows, rings, focus rings, machining rings, deposition rings, nozzles, injectors, gas injectors, showerheads, gas distribution plates, diffusers, ion suppressor elements, chucks, electrostatic wafer chucks (ESCs), and disks. Machining, drilling, boring, grinding, lapping, polishing, etc. as known to those skilled in the art may be performed as needed to form the sintered ceramic body into a component of a predetermined shape for use in a plasma processing chamber. The use of a powder mixture within the composition range as disclosed herein can provide a sintered ceramic body with improved machinability by using a CTE-matched layer, thereby reducing stress during the machining step of the disclosed method.

[0150] Optional surface preparation

[0151] In one embodiment, at least one surface of the sintered ceramic body may be polished before or after machining. Preferably, at least one surface is polished before machining as described above. Polishing the at least one surface includes the steps of grinding the at least one surface until the surface has (i) an average flatness of no more than 25 microns measured at angles of 0°, 90°, 180° and 270° on four quadrants of the at least one surface as measured using a spherometer, (ii) an Ra of less than 14 microinches, and (iii) an Rz of less than 160 microinches; after the grinding step, the at least one surface is polished with a lapping plate and a lapping medium slurry; after lapping, the at least one surface is continuously polished in a series of polishing steps until the at least one surface exhibits an Ra value of ≤2 microinches and an Rz of ≤2 microinches and an absolute value of flatness greater than 15 micrometers as measured using a spherometer, wherein the polishing is performed by typical methods known to those skilled in the art, i.e., lapping and continuous polishing by using finer particles of abrasives of controlled particle size (such as aluminum oxide and diamond).

[0152] Such polishing steps are fully described in U.S. patent application serial number 63 / 325,956 filed on March 31, 2022, the disclosure of which is incorporated herein by reference.

[0153] YAG sintered ceramic body

[0154] The sintered ceramic body comprises at least one layer, and thus in some embodiments is a single-layer sintered ceramic body, which contains 90% to 99.8% by volume of polycrystalline yttrium aluminum garnet (YAG) and has the characteristics disclosed herein. In other embodiments, the sintered ceramic body is a multilayer sintered ceramic body, which comprises at least one layer, and the at least one layer contains 90% to 99.8% by volume of polycrystalline yttrium aluminum garnet (YAG) and has the characteristics disclosed herein. In a multilayer embodiment, at least one layer containing 90% to 99.8% by volume of polycrystalline yttrium aluminum garnet (YAG) and having the characteristics disclosed herein is preferably an outer layer, so it can ultimately be the surface exposed to the plasma in the plasma processing chamber in use. The second layer can be any suitable material, such as zirconium oxide toughened aluminum oxide or yttrium oxide.

[0155] In an embodiment, by using materials and methods as disclosed herein, the sintered ceramic body includes at least one layer comprising polycrystalline YAG in an amount of 90 volume % to 99.6 volume %, preferably 90 volume to 99.4 volume %, preferably 95 volume % to 99.6 volume %, preferably 95 volume % to 99.4 volume % of a cubic crystal structure. In certain embodiments, the sintered ceramic body as disclosed herein may include 95 volume % to 99.6 volume % of a YAG cubic phase and 0.01% to 5% of an alumina phase. The volume values ​​of the YAG cubic phase as disclosed herein do not include any Al2O3 and zirconium-containing compounds. The embodiments of the sintered ceramic body as disclosed herein are polycrystalline, and thus the sintered ceramic body may include two or more crystals without limitation. The sintered ceramic body comprises a volume porosity in an amount of 0.1% to 4%, preferably 0.1% to 3%, preferably 0.1% to 2%, preferably 0.1% to 1% and preferably 0.1% to 0.5%, wherein if the porosity is less than 2%, the volume porosity is calculated from a density measurement performed according to ASTM B962-17 or ASTM B311-17.

[0156] In another embodiment, disclosed herein is a sintered ceramic body comprising a Y3Al5O 12 At least one layer of yttrium aluminum garnet (YAG) containing 90 volume % to 99.8 volume % of a cubic crystal structure and an amount of aluminum oxide of 0.2 volume % to 10 volume %, preferably 0.2 volume % to 8 volume %, preferably 0.2 volume % to 5 volume %, preferably 0.2 volume % to 3 volume %, preferably 0.2 volume % to 2 volume % and preferably 0.2 volume % to 1 volume %.

[0157] In embodiments, at least one layer of the sintered ceramic body comprises at least one form of polycrystalline yttrium aluminum oxide in an amount of 70% to 100% by volume (as determined by x-ray diffraction), a volume porosity of 0.1% to less than 5% (as calculated by density measurement according to ASTM B962-17), a purity greater than 99.99% (as measured by ICPMS method), and a hardness of at least 1200 HV (as measured according to ASTM standard C1327). In embodiments, at least one layer of the sintered ceramic body comprises at least one polycrystalline yttrium aluminum oxide phase or a combination of yttrium aluminum oxide phases, to include yttrium aluminum garnet Y3Al5O in specific embodiments. 12 (YAG) phase, yttrium aluminum perovskite YAlO3 (YAP) and yttrium aluminum monoclinic Y4Al2O9 (YAM) and combinations thereof. In a preferred embodiment, the sintered ceramic body comprises 90 volume % to 99.8 volume % of polycrystalline yttrium aluminum garnet (YAG).

[0158] In embodiments, at least one layer of a sintered ceramic body as disclosed herein may comprise about 100% of a single crystalline phase of any of the yttrium aluminum oxides of YAG, YAP, or YAM. In other embodiments, the sintered ceramic body may comprise a matrix or composite structure of two or more discrete or continuous phases of yttrium aluminum oxides as disclosed herein. In further embodiments, the sintered ceramic body may comprise a minor amount of aluminum oxide and / or yttrium oxide phases, with the majority being any or a combination of yttrium aluminum oxides of YAG, YAP, and YAM.

[0159] As a guide, Figure 1 A yttria / alumina binary phase diagram is depicted. The horizontal axis corresponds to the mixture ratio of yttria and alumina in mole percent, while the vertical axis is the temperature in degrees Celsius. The left side of the horizontal axis corresponds to 100% alumina, while the right side corresponds to 100% yttria. Figure 1 The phase diagram of illustrates the regions where the yttrium aluminum oxide phases of YAG, YAP, and YAM are formed and the conditions of molar composition and temperature necessary to produce these forms. The formation of YAG may require precise powder batching and careful processing in order to maintain stoichiometry and thus form a sintered ceramic body of phase-pure YAG containing 37.5 mol% yttrium oxide and 62.5 mol% aluminum oxide.

[0160] In an embodiment, at least one layer of a sintered ceramic body disclosed herein comprises 15 ppm to 500 ppm of zirconium as a dopant and has at least one surface that exhibits an L* value of 50 to 77, an a* value of 6 to 12, and a b* value of 3 to 6 after exposure to UV radiation. The purpose of adding (i.e., doping) zirconium is to achieve a uniform color change to red once the sintered ceramic body is exposed to UV radiation as described in detail below. In an embodiment, zirconium may be present in an amount of 15 ppm to 500 ppm, 15 ppm to 100 ppm, 15 ppm to 250 ppm, 50 ppm to 250 ppm, 50 ppm to 225 ppm, 50 ppm to 200 ppm, 50 ppm to 175 ppm, 50 ppm to 150 ppm, 50 ppm to 150 ppm, 50 ppm to 125 ppm, 50 ppm to 100 ppm, and 50 ppm to 75 ppm.

[0161] The above amounts of zirconium may be added as oxide, chloride, nitrate or any other counter ion. Preferably, zirconium is added as oxide.

[0162] At least one layer of the sintered ceramic body disclosed herein is very dense and correspondingly has a very small pore distribution, such that at least one surface comprises pores having a pore size not exceeding 5 μm. In embodiments, for at least 95% of the pores, the maximum pore size is 1.5 μm.

[0163] To evaluate the grain size of at least one first layer comprising polycrystalline YAG, linear intercept grain size measurements were performed according to the Heyn linear intercept procedure described in ASTM Standard E112-2010 "Standard Test Method for Determining Average Grain Size". Grain size measurements (as listed in Table 3) were performed, and average grain sizes ranging from 1.1 μm to 6.3 μm were measured in 25 repetitions. Maximum and minimum grain sizes ranging from 2 μm to 7.7 μm were also measured on the surface of at least one first layer comprising YAG. The integral multilayer sintered ceramic body may have a surface with a grain size of, for example, a maximum grain size of about 8 μm and less, preferably a maximum grain size of 6 μm and less. In an embodiment, the integral multilayer sintered ceramic body may have a surface with an average grain size of 0.4 μm to 6.5 μm, preferably 0.4 μm to 5 μm, preferably 0.4 μm to 3 μm, preferably 0.8 μm to 6.5 μm, preferably 0.8 μm to 5 μm, preferably 0.8 μm to 3 μm, preferably 1 μm to 7 μm, preferably 1 μm to 6.5 μm.

[0164] Table 3

[0165]

[0166] Density measurements were performed using the Archimedean buoyancy method according to ASTM B962-17 and ASTM B311-17 (when the porosity level is 2% and less). The reported density values ​​and standard deviations are the average of 5 or more measurements. The density of a commercially available YAG single crystal sample was measured using the method disclosed herein. The density of a commercially available bulk YAG single crystal sample was measured using the method disclosed herein. An Archimedean density of 4.56 g / cc was obtained in 5 measurements and this value was taken as the theoretical density of YAG as used herein. A sintered ceramic body comprising at least one layer of phase-pure YAG and additional phase-pure YAG comprising up to 1 wt. % excess alumina as disclosed in the embodiments herein can have a density of, for example, 4.374 g / cc to 4.556 g / cc, 4.419 g / cc to 4.556 g / cc, 4.465 g / cc to 4.556 g / cc, 4.510 g / cc to 4.556 g / cc, and 4.533 g / cc to 4.556 g / cc, or 96% to 99.999%, 97% to 99.999%, 98% to 99.999%, 99% to 99.999%, and 99.5% to 99.999% of the theoretical density of YAG. The corresponding volume porosity (Vp) may be 0.010% to less than 5%, 0.010% to 4%, 0.010% to 3%, 0.010% to 3%, 0.010% to 2%, 0.010% to 1%, preferably less than 1%, preferably less than 0.5%, as calculated in density measurements performed as disclosed herein. In an embodiment where the ceramic sintered body includes at least one second layer comprising about 16 volume % of at least one of stabilized zirconia and partially stabilized zirconia (with the balance being alumina), the density was measured under similar conditions and calculated to be about 4.32 g / cc. The theoretical density of a ZTA comprising about 16 volume % zirconia was calculated using the volume mixing rule, and a density of 4.32 was measured and taken as the theoretical density of at least one second layer comprising about 16 volume % zirconia. Therefore, the theoretical density percentage of at least one second layer of the multilayer sintered ceramic body containing about 16 volume % of zirconium oxide is 99% to 100%, preferably 99.5% to 100%, preferably about 100% of the theoretical density. The theoretical density percentage (also expressed as relative density, RD) of the multilayer sintered ceramic body disclosed according to this embodiment is greater than 99%, preferably 99% to 100%, preferably 99.5% to 100%, preferably about 100% of the theoretical density of the entire multilayer sintered ceramic body containing at least one first layer and at least one second layer.

[0167] The relative density (RD) of a given material is defined as the ratio of the measured density of the sample to the reported theoretical density of the same material as shown in the following formula. The volume porosity (Vp) is calculated from the density measurement as follows:

[0168]

[0169] Wherein psample is the measured (Archimedean) density according to ASTM B962-17, ptheoretical is the reported theoretical density, and RD is the relative fractional density. Using this calculation, porosity levels of 0.1% to 5% and less are calculated from the measured density values ​​of the sintered ceramic bodies as disclosed herein. Thus, in embodiments, the sintered ceramic bodies comprising at least one yttrium aluminum oxide garnet phase as disclosed herein include a volume porosity in the sintered ceramic body in an amount of 0.1% to 5%, preferably 0.1% to 4%, preferably 0.1% to 3%, preferably 0.1% to 2%, preferably 0.1% to 1%, as calculated from the corresponding density.

[0170] These density, purity, and porosity levels can provide enhanced resistance to erosion and corrosion caused by plasma etching and deposition processes. The disclosed methods and materials are particularly useful in preparing large-sized ceramic sintered bodies, such as a maximum dimension of 200 mm to about 625 mm. The high density, and thus high mechanical strength, of the ceramic sintered bodies also provide improved processability, especially at large sizes. Successful manufacture of sintered yttrium aluminum oxide bodies, and particularly bodies including layers formed of phase-pure YAG in the range as disclosed herein, in the longest dimension (about 200 mm to about 625 mm) can be achieved by controlling the density variation in at least one of the longest dimensions. An average density of 96% and greater is desired, with a density variation of 0.2% to less than 5% and less, preferably 4% and less, preferably 3% and less, preferably 2% and less, and preferably 1% and less, as measured in the largest dimension, whereby the largest dimension may be, for example, 100 mm to 625 mm, preferably 100 mm to 622 mm, preferably 100 mm to 575 mm, preferably 200 mm to 625 mm, preferably 200 mm to 510 mm, preferably 400 mm to 625 mm, and preferably 500 mm to 625 mm. The thickness, i.e. the dimension perpendicular to the longest dimension, may be in the range of 12 mm to 40 mm, preferably 16 mm to 36 mm, more preferably 20 mm to 32 mm, and even more preferably 24 mm to 28 mm, and still more preferably 25 mm to 27 mm. Low densities, less than 95% of the theoretical density of YAG, may have lower strength and, thus, higher porosity (over 5%), which leads to cracking and poorer processability.

[0171] In addition to high density, the density variation of the disclosed ceramic sintered bodies over the largest dimension can affect the ability to be handled, machined, and used as ceramic sintered parts, especially at large dimensions (>100 mm).The density was measured over the largest dimension of several examples of ceramic sintered bodies as disclosed herein.

[0172] In addition to high density, high hardness values ​​can also provide enhanced erosion resistance during use as plasma chamber components. Therefore, Vickers hardness measurements were performed according to ASTM Standard C1327 "Standard Test Method for Vickers Indentation Hardness of Advanced Ceramics". The test equipment used for all hardness measurements was a Wilson microhardness tester model VH1202. For the ceramic sintered bodies as disclosed herein, the hardness values ​​that can be obtained are at least 1200 HV, preferably at least 1400 HV, preferably at least 1800 HV, preferably at least 2000 HV, 1300 HV to 1600 HV, 1300 HV to 1500 HV, 1300 HV to 1450 HV, 1300 HV to 1400 HV, 1400 HV to 1600 HV, 1450 HV to 1600 HV, 1450 HV to 1550 HV. The measured values ​​obtainable using the Vickers hardness method known in the art are converted into SI units of GPa. For the ceramic sintered bodies as disclosed herein, the obtainable hardness values ​​are 12.75 GPa to 15.69 GPa, 12.75 GPa to 14.71 GPa, 12.75 GPa to 14.22 GPa, 12.75 GPa to 13.73 GPa, 13.73 GPa to 15.69 GPa, 14.22 GPa to 15.69 GPa, preferably 14.22 GPa to 15.20 GPa. These high hardness values ​​can help to enhance the resistance to ion bombardment during the semiconductor etching process and reduce erosion during use, thereby providing extended life when the ceramic sintered bodies are machined into ceramic sintered parts with fine-scale features.

[0173] In one embodiment, the sintered ceramic bodies disclosed herein have an average hardness of 13.0 GPa to 15.0 GPa for eight samples using an applied load of 0.2 kgf as measured according to ASTM Standard C1327. In another embodiment, the ceramic sintered bodies disclosed herein have an average hardness of about 13.5 GPa to 14.5 GPa for eight samples using an applied load of 0.2 kgf as measured according to ASTM Standard C1327.

[0174] It is known that mechanical strength properties improve with decreasing grain size. To assess grain size, linear intercept grain size measurements are performed according to the Heyn linear intercept procedure described in ASTM Standard E112-2010 "Standard Test Method for Determining Average Grain Size". Grain size can also be measured by SEM. In order to meet the requirements of high flexural strength and rigidity for use in reaction chambers as large components of 200 mm to 625 mm, the fine grain size of the ceramic sintered body may be, for example, a maximum grain size of about 10 μm and less, preferably a maximum grain size of 8 μm and less, preferably an average grain size of 5 μm and less, preferably 3 μm and less, preferably 2 μm and less, preferably 1.5 μm and less, preferably 1.0 μm and less, preferably an average grain size of 0.5 μm to 8 μm, preferably a grain size of 1 μm to 5 μm.

[0175] At least one layer comprising 90% to 99.8% by volume of polycrystalline yttrium aluminum garnet (YAG) may have a total impurity content of less than 100 ppm, preferably less than 75 ppm, less than 50 ppm, preferably less than 25 ppm, preferably less than 15 ppm, preferably less than 10 ppm, preferably less than 8 ppm, preferably less than 5 ppm, preferably 5 to 30 ppm, and preferably 5 to 20 ppm, relative to the total mass of at least one first layer comprising polycrystalline YAG measured using the ICPMS method. The total impurity content disclosed herein does not include Si in the form of silicon dioxide.

[0176] The detection limit of the presence of lighter elements identified using the ICP-MS method as disclosed herein is higher than the reporting limit of heavier elements. In other words, heavier elements such as Sc and higher are detected with higher accuracy (e.g., as low as 0.06ppm) compared to those lighter elements such as from Li to Al (e.g., detected with an accuracy as low as 0.7ppm). Therefore, the impurity content of those powders containing lighter elements such as from Li to Al can be determined to be about 0.7ppm and greater, and the impurity content of heavier elements from Sc (scandium) to U (uranium) can be determined to be about 0.06ppm and greater. Using the ICPMS method as disclosed herein, silicon dioxide as low as an amount of about 14ppm can be detected, while K (potassium) and Ca (calcium) of 1.4ppm and greater amounts can be identified. Iron can be accurately detected in an amount as low as 0.14ppm.

[0177] The sintered ceramic body as disclosed herein can be a single-layer sintered ceramic body, or it can be a layer of a multi-layer sintered ceramic body, comprising at least one layer of the sintered ceramic body containing 90 volume % to 99.8 volume % of polycrystalline yttrium aluminum garnet (YAG), wherein the at least one layer comprises at least one surface, wherein the at least one surface comprises pores having a pore size not exceeding 5 μm, and for at least 95% of the pores, the maximum pore size is 1.5 μm.

[0178] If the multilayer sintered ceramic body includes one or more additional layers, the one or more additional layers can be, for example, one or more of the following: (i) aluminum oxide, wherein the aluminum oxide contains at least one of stabilized zirconium oxide and partially stabilized zirconium oxide; (ii) an additional YAG layer; (iii) yttrium oxide; and (iv) aluminum oxide.

[0179] In some embodiments, at least one first layer comprising YAG may have a purity of 99.99% and higher, preferably 99.995% and higher (excluding Al2O3 and zirconium-containing compounds), each relative to a material having 100% purity, as measured using an ICPMS method as disclosed herein.

[0180] The above-mentioned characteristics of the corrosion-resistant component formed by the ceramic sintered body are achieved by adjusting the purity of the powders of yttrium oxide and aluminum oxide, the combination of the powders, the calcination of the powders, the pressure of the powders of yttrium oxide and aluminum oxide, the temperature of the powders of yttrium oxide and aluminum oxide, the duration of the powder sintering, the temperature of the ceramic sintered body / ceramic sintered component during the optional annealing step, and the duration of the optional annealing step. The method disclosed herein is suitable for producing ceramic sintered bodies, especially those of large size, using a scalable manufacturing process.

[0181] The methods and compositions disclosed herein will be illustrated in more detail with reference to the following examples, but it should be understood that it is not to be construed as being limited thereto.

[0182] Example

[0183] The following examples are included to more clearly demonstrate the general nature of the present disclosure.These examples of the present disclosure are exemplary and not limiting.

[0184] The measurements of all embodiments were carried out using the disclosed apparatus and methods. Purity measurements were carried out using the ICP-MS of the Agilent 7900ICP-MS model G8403. The specific surface area (SSA) of the powder and powder mixture was measured using the Horiba BET surface area analyzer model SA-9601. Specific surface area measurements were carried out according to ASTM C1274. Particle size was measured using the Horiba model LA-960 laser scattering particle size distribution analyzer capable of measuring particle sizes from 10nm to 5mm. For all embodiments, and in view of the need to minimize contamination, the total concentration of undesirable elements in the raw materials used was at most 1 atom %.

[0185] The sintered ceramic bodies prepared in the following examples were circular and had a diameter of 622.3 mm.

[0186] Example 1 YAG

[0187] The specific surface area is 4.5m 2 / g to 6m 2 / g, yttrium oxide powder (purity 99.9984%, impurities about 16 ppm relative to mass), d10 particle size of 2.0 μm to 3.5 μm, d50 particle size of 4.0 μm to 6.5 μm and d90 particle size of 6.5 μm to 10 μm) and a specific surface area of ​​6 m 2 / g to 8m 2 Alumina powder (purity of about 99.9995% and impurities of about 5 ppm relative to mass) of 0.075 μm to 0.2 μm, d10 particle size of 0.075 μm to 0.2 μm, d50 particle size of 2.5 μm to 5.5 μm and d90 particle size of 15 μm to 22 μm are combined in a certain molar ratio to form a powder mixture, which reacts when sintered to form a ceramic sintered body containing a cubic yttrium aluminum garnet (YAG) phase. A high purity alumina medium ( > 99.9% as measured by ICPMS), and ethanol was added in an amount of about 35% by weight of the combined weight of ethanol and powder to form a slurry. Tumbling mixing or upside-down mixing, known to those skilled in the art, was performed for a duration of 20 hours, and then ethanol was extracted from the powder mixture using rotary evaporation according to known methods. After calcination at 1050° C. in air for 6 hours, the calcined powder mixture was measured to have 4 m 2 / g to 6m 2 / g of specific surface area. According to methods known to those skilled in the art, the powder, powder mixture and / or calcined powder mixture can be sieved, calcined, blended and / or ground using an aperture of 45μm to 400μm in different process steps. The purity is measured using the ICPMS method as disclosed herein, and it is measured that the total impurity content of the calcined powder mixture is about 5ppm relative to the total mass of the oxides calculated from all components, which corresponds to a purity of about 99.9995%. The purity limits and impurity contents of the starting powders of yttrium oxide and aluminum oxide and the calcined powder mixture as disclosed herein do not include Si. As disclosed herein, the detection limit of the purity of Si measured using the ICPMS method is about 14ppm, so the starting powders of yttrium oxide and aluminum oxide and the calcined powder mixture can contain Si in the form of silicon dioxide at a detection level of about 14ppm. The calcined powder mixture is arranged in a volume defined by a tool set of a sintering device as disclosed herein, and 10 -2 Support up to 10 -3 The sintered powder mixture was heated from ambient temperature to 800°C at a rate of about 10°C / min, and then the pressure was ramped up at a rate of about 0.4MPa / min to about 0.6MPa / min, and the temperature was ramped up as described above to reach sintering conditions of 1600°C and 15MPa for 60 minutes to form a polycrystalline YAG sintered ceramic body in the shape of a disk with a maximum size of 150mm. Density measurements were performed on the sintered and annealed samples according to ASTM B962-17. The average density was 4.549g / cc in 5 measurements. This corresponds to 99.854% of the theoretical density of YAG (reported herein as 4.556g / cc) and a corresponding volume porosity of 0.146%, as calculated from density measurements. The processed sample has the appearance of a dark gray ceramic with a slight transparency when ground thinner for light penetration. A heating rate of 1°C / min - 5°C / min was used to 1400°C and the sample was then oxidized at 1400°C for 8 hours, resulting in a translucent white material.

[0188] Example 2 : Particle size distribution is not optimal

[0189] Alumina batch number 21307 has Fig. 9 The particle size distribution is shown in . Fig. 9 The BET and values ​​are listed below.

[0190] BET (surface area) 7.74

[0191] d10(μm)0.9626

[0192] d50(μm)2.6778

[0193] d90(μm)5.9797

[0194] In a 5 gallon kettle and bucket, 4.775 kg of alumina was mixed with 6.282 kg of yttrium oxide in 9 liters of ethanol, tumbled with alumina grinding media, processed by rotary evaporator at 60° C. for 60 minutes, and then at 75° C. for 120 minutes, and dried in an oven at 120° C. for 8 hours. The mixture was then calcined.

[0195] Five kilograms of the calcined powder were placed in a 622.3 mm circular die and sintered at 1625° C. by field assisted sintering under a pressure of several tons in vacuum conditions. Specifically, the calcined powder was placed in a volume defined by a tool set of a sintering apparatus as disclosed herein, and 10 -2 Support up to 10 -3 A vacuum condition of torr. A pressure of 5 MPa is applied, and the calcined powder mixture in the volume is heated from ambient temperature to 800°C at a rate of about 10°C / minute, and then the pressure is ramped up at a rate of about 0.4 MPa / minute to about 0.6 MPa / minute, and the temperature continues to ramp up as before to reach sintering conditions of 1625°C and 15 MPa for 60 minutes to form a polycrystalline YAG sintered ceramic body in the shape of a disk with a maximum dimension of 622.3 mm. The thickness of the YAG is 4 mm to 5 mm. The thickness may be 5 mm to 30 mm, or greater. Alumina and yttrium oxide react to form YAG, but include regions of unreacted yttrium oxide and alumina, such as Fig.10 As shown in the SEM image (the white area is unreacted yttrium oxide, and the dark area is unreacted aluminum oxide):

[0196] Example 3 : Best particle size distribution

[0197] Alumina batch number 21182 has Fig.11 The particle size distribution is shown in . Fig.11 The BET and values ​​are listed below.

[0198] BET (surface area) 9.89

[0199] d10(μm)0.5007

[0200] d50(μm)2.4601

[0201] d90(μm)6.7047

[0202] In a 5 gallon kettle and bucket, 4.775 kg of alumina was mixed with 6.282 kg of yttrium oxide in 9 liters of ethanol, tumbled with alumina grinding media, processed by rotary evaporator at 60° C. for 60 minutes, and then at 75° C. for 120 minutes, and dried in an oven at 120° C. for 8 hours. The mixture was then calcined.

[0203] Five kilograms of the calcined powder mixture was placed in a 650 mm circular mold and sintered at 1625° C. by field-assisted sintering under a pressure of several tons under vacuum conditions. Specifically, the calcined powder was placed in a volume defined by a tool set of a sintering apparatus as disclosed herein, and 10 -2 Support up to 10 -3 A vacuum condition of 1000 torr is applied. A pressure of 5 MPa is applied, and the calcined powder mixture in the volume is heated from ambient temperature to 800°C at a rate of about 10°C / min, and then the pressure is ramped up at a rate of about 0.4 MPa / min to about 0.6 MPa / min, and the temperature continues to ramp up at the aforementioned rate to reach sintering conditions of 1625°C and 15 MPa for 60 minutes to form a polycrystalline YAG sintered ceramic body in the shape of a disk with a maximum size of 622.3 mm. Alumina and yttrium react to form YAG. As Fig.12 As shown in , there is no unreacted yttria visible in the SEM image of the YAG. Only areas of unreacted alumina are visible, which is expected because the ratio of alumina to yttria is alumina-rich and produces Fig.12 The desired microstructure shown in .

[0204] Example 4 : Balanced stoichiometry

[0205] Three hundred grams of a stoichiometrically balanced calcined powder mixture of alumina and yttrium oxide for forming YAG was placed in a 100 mm circular mold and sintered at 1550° C. by field-assisted sintering under a pressure of several tons under vacuum conditions. The alumina in the calcined powder mixture had a Fig.13 The calcined powder is placed in a volume defined by a tool set of a sintering apparatus as disclosed herein, and 10 -2 Support up to 10 -3A vacuum condition of 1000 torr is applied. A pressure of 5 MPa is applied, and the calcined powder mixture in the volume is heated from ambient temperature to 800°C at a rate of about 10°C / min, and then the pressure is ramped up at a rate of about 0.4 MPa / min to about 0.6 MPa / min, and the temperature continues to ramp up at this rate to reach sintering conditions of 1550°C and 30 MPa for 30 minutes to form a polycrystalline YAG sintered ceramic body in the shape of a disk with a maximum size of 100 mm and a thickness of 7 mm. Alumina and yttrium react to form YAG. As Fig.14 As shown in , there is no unreacted yttrium oxide visible in the SEM image of the YAG. Only small areas of unreacted aluminum oxide are visible. Based on the amount of unreacted aluminum oxide visible in the SEM image, the microstructure is 99.905% crystalline YAG.

[0206] Example 5 : Alumina-rich stoichiometry

[0207] Two hundred grams of alumina-rich calcined powder mixture of alumina and yttria for forming YAG was placed in a 100 mm circular mold and sintered at 1625° C. by field-assisted sintering under a pressure of several tons under vacuum conditions. Specifically, two hundred grams of alumina-rich calcined powder was obtained by mixing 219.3 grams of alumina with 282.93 grams of yttria in 700 ml of ethanol and grinding with 500 grams of 10 mm alumina media at 200 rpm for 16 hours. The mixture was then rotary evaporated and sieved with -40 mesh and calcined. The alumina powder used to form the mixture had a particle size of 1.34 mm. Fig.15 After calcination, the powder mixture is placed in a volume defined by a tool set of a sintering apparatus as disclosed herein, and 10 -1 Support up to 10 -3 A vacuum condition of 100 torr is applied. A pressure of 15 MPa is applied, and the calcined powder mixture in the volume is heated from ambient temperature to 800°C at a rate of about 10°C / min, and then the pressure is ramped up at a rate of about 0.4 MPa / min to about 0.6 MPa / min, and the temperature continues to ramp up at this rate to reach sintering conditions of 1625°C and 15 MPa for 90 minutes to form a polycrystalline YAG sintered ceramic body in the shape of a disk with a maximum size of 100 mm. Alumina and yttrium oxide react to form YAG. As Fig.14 As shown in , there is no unreacted yttrium oxide visible in the SEM image of the YAG. Only areas of unreacted alumina are visible, which is expected since the powder is rich in alumina, at about 0.5 mol% alumina.

[0208] Based on the data shown in the foregoing examples and the accompanying drawings, it has been shown that the alumina powder must have a certain range of particle sizes to match the Figure 2The yttrium of the particle size distribution in the reaction is reacted to form YAG substantially free of unreacted yttrium. Specifically, the fine-grained aluminum oxide ( Figure 4 and Figure 5 The curve marked with circles in FIG. 1 ) leaves unreacted yttrium. It is believed that the fine alumina particles react too quickly with the yttrium during sintering and surround some areas of yttrium with YAG, which prevents the reaction of the surrounded yttrium areas. If the alumina includes a mixture of fine particles and larger particles, it is believed that the larger particles of alumina slow down the reaction during sintering, allowing more yttrium to react with the alumina ( Figure 4 and Figure 5 However, if Figure 4 and Figure 5 As shown by the curve marked with triangles in FIG. 1 , there cannot be too many larger particles relative to the smaller particle sizes.

[0209] A number of embodiments as disclosed herein have been described. However, it should be understood that various modifications may be made without departing from the spirit and scope of the embodiments disclosed herein. Therefore, other embodiments are within the scope of the following claims.

Claims

1. A method for preparing a sintered ceramic body, the method comprising the following steps: a. mixing yttrium oxide powder and aluminum oxide powder to prepare a mixture, wherein i. the yttrium oxide powder is characterized by a particle size distribution wherein at least 50% by volume of the particles are less than 15 microns in size and the remaining particles are between 1 micron and 23 microns in size, and ii. the alumina powder is characterized by a multimodal particle size distribution, the multimodal particle size distribution comprising a first maximum and a second maximum of particle sizes on the particle size distribution as a percentage of the amount of particle sizes, wherein one of the first maximum and the second maximum is within a particle size range of 0.75 microns to 1.35 microns, and the one of the first maximum and the second maximum has a particle size greater than the particle size of the other maximum; b. disposing the mixture within a volume defined by a tool set of a sintering apparatus to form at least one layer of the mixture and to create a vacuum condition within the volume; c. applying pressure to the at least one layer of the mixture while heating to a sintering temperature and sintering to form a sintered ceramic body, the sintered ceramic body comprising the at least one layer, the at least one layer comprising 99 volume % to more than 99.9 volume % of polycrystalline yttrium aluminum garnet (YAG); and d. Lowering the temperature of the sintered ceramic body.

2. The method of claim 1, wherein 15% of the particles of the aluminum oxide powder have a size less than 0.5 microns, 50% of the particles of the aluminum oxide powder have a size less than 2 microns, and 100% of the particles of the aluminum oxide powder have a size less than 15 microns. 3 . The method of claim 2 , wherein the first maximum value and the second maximum value are expressed as percentages of an amount of particles, wherein a ratio of the first maximum value to the second maximum value is greater than three. The method of claim 2 , wherein the first maximum is a particle size between 3 μm and 5.5 μm.

5. The method of claim 2, wherein the second maximum is a particle size less than 0.0004 microns. The method of claim 2 , wherein the multimodal particle size distribution comprises a third maximum. The method of claim 1 , wherein a ratio of the first maximum value to the third maximum value is between 2:3 and 9:

1.

8. A method for producing a less than 1% alumina-rich YAG layer in a sintered ceramic body, wherein the YAG layer is substantially free of unreacted yttria, YAP and YAM, the method comprising: a) providing an alumina powder comprising alumina particles having a diameter no greater than 23 microns, and wherein 5% to 40% of the alumina particles have a diameter less than 1 micron; b) providing yttrium oxide powder; c) combining the yttrium oxide powder and the aluminum oxide powder at a molar ratio of yttrium oxide to aluminum oxide of less than 3:5 to form a yttrium oxide and aluminum oxide mixture; d) placing the mixture in a cylindrical volume defined by a tool set of a sintering apparatus to form at least one layer of the mixture, wherein the cylindrical volume has a diameter greater than 100 mm and a vacuum condition is created in the volume; as well as e) applying uniaxial pressure to the calcined mixture in the cylindrical volume while heating to a sintering temperature and sintering to form a sintered ceramic body comprising the at least one layer in which the yttrium oxide and aluminum oxide particles have been combined with each other to form 99 volume percent or more of polycrystalline yttrium aluminum garnet (YAG).

9. The method of claim 8, further comprising, prior to said disposing the yttrium oxide and aluminum oxide mixture within a cylindrical volume, performing a non-reactive calcination of the mixture by raising the temperature to a calcination temperature and maintaining the calcination temperature for a period of time to calcine the mixture.

10. The method of claim 8, wherein providing an aluminum oxide powder comprises providing an aluminum oxide powder having a multimodal particle size distribution comprising at least two maxima in particle size.

11. The method according to claim 8, wherein providing aluminum oxide powder comprises: providing a first aluminum oxide powder having particles having a diameter less than 7 microns, the first aluminum oxide powder particles comprising a first diameter distribution consisting of a single maximum value expressed as a percentage of the amount of the first aluminum oxide powder particles, the single maximum value being within a range between 0.2 microns and 0.4 microns; providing a second aluminum oxide powder having particles having a diameter less than 11 microns, the second aluminum oxide powder particles comprising a second diameter distribution, the distribution comprising an absolute maximum value expressed as a percentage of the amount of the second aluminum oxide powder particles, the absolute maximum value being within a range of 3.4 microns to 4.4 microns; and The first alumina powder and the second alumina powder were mixed together in a ratio of 4:1 by weight.

12. The method of claim 8, wherein providing an aluminum oxide powder comprises providing an aluminum oxide powder having a multimodal particle size distribution comprising at least three maxima in particle size.

13. The method of claim 9, wherein the first maximum is a particle size between 3 microns and 5.5 microns. The method according to claim 13 , wherein the first maximum value is an absolute maximum value expressed as a percentage of the amount of particles. The method according to claim 9 , wherein the second maximum value is 0.7 μm to 1.5 μm. 16 . The method of claim 9 , wherein a ratio of the first maximum value to the second maximum value is in a range between 2:3 and 9:

1.

17. A composition for sintering YAG, the composition comprising a mixture of yttrium oxide and aluminum oxide powders, wherein i. The yttrium oxide powder comprises particles falling within a size range between 0 microns and 23 microns; ii. the alumina powder comprises particles falling within a size range between 0 microns and 12 microns; and iii. Each of the aluminum oxide powder and the yttrium oxide powder comprises a particle size distribution comprising d50, d10 and d90, wherein a ratio of the d50 of the yttrium oxide powder to the d50 of the aluminum oxide powder falls within a range between 2.64:1 and 6.89:1, a ratio of the d90 of the yttrium oxide powder to the d90 of the aluminum oxide powder falls within a range between 3.4:1 and 17:1, and a ratio of the d10 of the yttrium oxide powder to the d10 of the aluminum oxide powder falls within a range between 1.7:1 and 5:

1.

18. The composition of claim 17, wherein the aluminum oxide powder further comprises a first maximum and a second maximum in particle size on an aluminum oxide particle size distribution measured as a percentage of the particle size by amount.

19. The composition of claim 17, wherein the yttrium oxide powder and the aluminum oxide powder are present in a molar ratio of yttrium oxide to aluminum oxide of less than 3:

5.

20. The composition of claim 17, wherein the yttrium oxide powder and the aluminum oxide powder are present in a molar ratio of yttrium oxide to aluminum oxide of 3:5 to 3:5.025.

Citation Information

Patent Citations

  • Apparatus for hot wall reactive ion etching using a dielectric or metallic liner with temperature control to achieve process stability

    US5798016A

  • Plasma processing apparatus

    US5911852A

  • Ceramic composition for an apparatus and method for processing a substrate

    US6123791A

  • Ceramic composition for an apparatus and method for processing a substrate

    US6352611B1

  • Preparation method of polycrystalline block material used for optical wavelength conversion

    CN110395977A